Alkaline iron battery electrodes

JP7936802B2Active Publication Date: 2026-10-16FORM ENERGY INC
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2023542515
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-01-13
Filing Date
2022-01-12
Publication Date
2026-10-16
Estimated Expiration
2042-01-12

Smart Images

  • Figure 0007936802000009
    Figure 0007936802000009
  • Figure 0007936802000010
    Figure 0007936802000010
  • Figure 0007936802000011
    Figure 0007936802000011
Patent Text Reader

Abstract

Various embodiments may include a battery electrode comprising an iron electrode body comprising an iron active material and a zinc sulfide additive, the zinc sulfide additive comprising crystalline cubic zinc sulfide. Various embodiments may include a battery electrode comprising an iron electrode body comprising an iron active material and a manganese sulfide additive, the manganese sulfide additive comprising crystalline cubic manganese sulfide. Various embodiments may include an iron electrode battery comprising an iron electrode and a sulfide reservoir separated from the iron electrode, the sulfide reservoir comprising crystalline cubic zinc sulfide. Various embodiments may include an iron electrode battery comprising an iron electrode and a sulfide reservoir separated from the iron electrode, the sulfide reservoir comprising crystalline cubic manganese sulfide.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] This application claims priority to U.S. Provisional Patent Application No. 63 / 136,746, entitled “Electrodes for Alkaline Iron Batteries,” filed on 13 January 2021, the contents of which are incorporated herein by reference in their entirety for any purpose. This application also relates to subject matter disclosed in International Publication No. 2019133702 (hereinafter “Pham Publication '702”), published on 4 July 2019, the contents of which are incorporated herein by reference in their entirety for any purpose to the extent that they are not consistent with the disclosures herein.

[0002] The present invention relates in general to battery electrodes, and more specifically to battery electrodes having an iron active material. [Background technology]

[0003] Energy storage technologies are playing an increasingly important role in power grids. At its most basic level, these energy storage assets provide smoothing to better match generation and demand in the distribution grid. The services performed by energy storage devices are beneficial to the power grid across multiple timescales, from milliseconds to days. Battery sizes range from watts for backup power supplies to kilowatts for communication systems and megawatts for large-scale distribution networks.

[0004] This "Background Art" section is intended to introduce various aspects of the art that may be relevant to embodiments of the present invention. Accordingly, the above considerations in this section are intended to provide a framework for a better understanding of the present invention and should not be considered an endorsement of prior art. [Overview of the Initiative]

[0005] Various embodiments of systems and methods for the manufacture and use of additives that have been found to be particularly useful for enhancing the performance of iron electrode batteries are provided herein. The additives generally consist of substantially all zinc sulfide (also represented herein by the chemical formula "ZnS") and / or manganese sulfide (also represented herein by the chemical formula "MnS") in a specific crystalline form.

[0006] Various embodiments include a battery electrode comprising an iron electrode body containing an iron active material and a zinc sulfide additive, wherein the zinc sulfide additive contains crystalline cubic zinc sulfide.

[0007] Various embodiments include a battery electrode comprising an iron electrode body containing an iron active material and a manganese sulfide additive, wherein the manganese sulfide additive contains crystalline cubic manganese sulfide.

[0008] Various embodiments include an iron electrode battery comprising an iron electrode and a sulfide reservoir separated from the iron electrode, wherein the sulfide reservoir contains crystalline cubic zinc sulfide.

[0009] Various embodiments include an iron electrode battery comprising an iron electrode and a sulfide reservoir separated from the iron electrode, wherein the sulfide reservoir contains crystalline cubic manganese sulfide.

[0010] The novel features of this invention are specifically described in the following claims. A further understanding of the features and advantages of this specification can be obtained by referring to the detailed description of the following exemplary embodiments utilizing the principles of this specification, and to the accompanying drawings. [Brief explanation of the drawing]

[0011] [Figure 1A] This figure shows examples of electrochemical cells that can serve as iron electrode batteries according to various embodiments.

[0012] [Figure 1B]Fig. 1 is a diagram showing an example of an electrochemical cell that can be an iron electrode battery according to aspects of various embodiments.

[0013] [Figure 1C] Fig. 2 is a series of schematic diagrams showing the change in sulfide concentration during the soaking time of samples having zinc sulfide solid and liquid electrolytes in various ratios.

[0014] [Figure 2A] Fig. 3 is a schematic diagram of X-ray diffraction spectra showing two samples of iron electrodes containing an "unstructured" cubic zinc sulfide additive and a "crystalline" zinc sulfide additive.

[0015] [Figure 2B] Fig. 4 is a schematic diagram showing an enlarged view of the XRD peak labeled 200 in FIG. 2A, showing the difference in full width at half maximum (FWHM) values of the peaks of the two samples.

[0016] [Figure 3] Fig. 5 is a schematic diagram showing the range of FWHM values for selected peak positions of samples of unstructured cubic ZnS and crystalline cubic ZnS.

[0017] [Figure 4] Fig. 6 is a diagram showing various exemplary systems in which one or more aspects of various embodiments can be used as part of a bulk energy storage system. [Figure 5] Fig. 7 is a diagram showing various exemplary systems in which one or more aspects of various embodiments can be used as part of a bulk energy storage system. [Figure 6] Fig. 8 is a diagram showing various exemplary systems in which one or more aspects of various embodiments can be used as part of a bulk energy storage system. [Figure 7] Fig. 9 is a diagram showing various exemplary systems in which one or more aspects of various embodiments can be used as part of a bulk energy storage system. [Figure 8]This figure shows various exemplary systems in which one or more of the various embodiments can be used as part of a bulk energy storage system. [Figure 9] This figure shows various exemplary systems in which one or more of the various embodiments can be used as part of a bulk energy storage system. [Figure 10] This figure shows various exemplary systems in which one or more of the various embodiments can be used as part of a bulk energy storage system. [Figure 11] This figure shows various exemplary systems in which one or more of the various embodiments can be used as part of a bulk energy storage system. [Figure 12] This figure shows various exemplary systems in which one or more of the various embodiments can be used as part of a bulk energy storage system. [Modes for carrying out the invention]

[0018] Various embodiments will be described in detail with reference to the accompanying drawings. References to specific examples and implementations are illustrative and not intended to limit the scope of the invention or claims. Wherever possible, the same reference numerals will be used throughout the drawings to refer to the same or similar parts. References to specific examples and implementations are illustrative and not intended to limit the scope of the claims. The following description of embodiments of the present invention is not intended to limit the invention to such embodiments, but rather to enable those skilled in the art to manufacture and use the invention. Unless otherwise noted, the accompanying drawings are not drawn to scale.

[0019] The following examples are provided to illustrate various embodiments of the system and method of the present invention. These examples are illustrative, may be predictive, and should not be considered limiting, nor should they limit the scope of the invention in any way.

[0020] It should be noted that it is not necessary to provide or express the theories underlying any novel, groundbreaking processes, materials, performances, or other beneficial features and properties that are the subject matter of or associated with embodiments of the present invention. Nevertheless, various theories are provided herein to further advance the art of the art. The theories presented herein do not in any way limit, restrict, or narrow the scope of protection granted to the claimed invention unless otherwise expressly stated. Such theories may not be necessary for the use of the present invention, nor may they be practiced. Furthermore, it is understood that the present invention may be linked to new and previously unknown theories for describing the functional characteristics of embodiments of the methods, articles, materials, devices, and systems of the present invention. Such subsequently developed theories do not limit the scope of protection granted to the present invention.

[0021] Various embodiments of the systems, equipment, techniques, methods, activities, and operations shown herein can be used in various other activities and fields in addition to those shown herein. In addition, such embodiments can be used, for example, with other equipment or activities that may be developed in the future, and with existing equipment or activities that may be partially modified based on the teachings herein. Furthermore, the various embodiments and examples shown herein can be used together with each other, whole or in part, and in various different combinations. Thus, the configurations provided in the various embodiments herein can be used together with each other. For example, the elements of an embodiment having A, A', and B, and the elements of an embodiment having A'', C, and D can be used together with each other in various combinations, for example, A, C, D, and A, A'', C, D, etc., according to the teachings herein. Thus, the scope of protection given to the present invention should not be limited to specific embodiments, examples, or specific embodiments, configurations, or arrangements shown in specific figures.

[0022] Where used herein, unless otherwise stated, room temperature is 25°C, and standard temperature and standard pressure are 25°C and 1 atm. Unless otherwise expressly stated, all tests, test results, physical properties, and values ​​that are temperature-dependent, pressure-dependent, or both are provided at standard ambient temperature and pressure.

[0023] Various embodiments of systems and methods for the manufacture and use of additives found to be particularly useful for enhancing the performance of iron electrode batteries are provided herein. The additives generally consist of substantially all zinc sulfide (also represented herein by the chemical formula "ZnS") and / or manganese sulfide (also represented herein by the chemical formula "MnS") in specific crystalline forms. As further detailed below, crystalline cubic ZnS has been found to produce a dissolved sulfide concentration an order of magnitude lower in 6M KOH than other crystalline forms of ZnS. This lower sulfide concentration allows the electrolyte sulfide concentration to be maintained for extended periods within the ideal range in which extended life and enhanced performance of iron electrode batteries have been confirmed. Various examples and embodiments of iron electrode batteries containing ZnS, substantially all of which are in the form of crystalline cubic ZnS, are also described herein. Crystalline cubic MnS is conceivable to produce similar results herein.

[0024] While not bound by theory, considerations regarding the credibility or understanding of fundamental principles may be present herein with respect to the devices and methods disclosed herein. The inventors recognize that regardless of the ultimate correctness of any mechanistic explanation or hypothesis, embodiments of the present invention may still be effective and useful.

[0025] As used herein, the term “iron electrode” refers to a porous or non-porous, rigid or flexible conductive structure containing an iron active material that can participate in electrochemical reactions in electrochemical devices such as primary or secondary batteries, electrolytic devices, or other electrochemical cells. Iron electrodes can be manufactured by any available technique or combination of techniques, such as sintering, hot pressing, cold pressing, wet paste lamination, dry pressing, slurry coating, PTFE-based processes, roll bonding, tape casting (blade coating) pocket filling, or other suitable processes. In various embodiments, iron electrodes may also include materials such as additive materials, pore-forming agents, binders, current collectors, support materials, and conductivity-enhancing additives.

[0026] As used herein, the term “iron active material” refers to an iron-containing material capable of oxidation reactions during the discharge of an electrochemical cell and / or reduction reactions during the charging of an electrochemical cell. Specifically, iron active materials include metallic iron (Fe) and / or one or more iron hydroxides (e.g., Fe(OH)2, Fe(OH)3, etc.), anhydrous and / or hydrated iron oxyhydroxides (e.g., FeOOH; e.g., FeO(OH)·nH2O, where n is the number of water molecules in the hydrated iron hydroxide molecule), iron oxides, suboxides, mixed oxides, e.g., FeO (wustite), FeO2 (iron dioxide), Fe2O3, Fe3O4 (magnetite), Fe4O5, Fe5O6, Fe5O7, Fe 25 O 32 Fe 13 O 19 Examples include any polymorphs (one or more) of these, and / or any combination thereof, such as other iron-containing compounds.

[0027] As used herein, the term “iron electrode battery” refers to a primary (disposable, discharge-only) or secondary (rechargeable) battery containing an iron active material that undergoes oxidation-reduction at the negative electrode of the battery. In some embodiments, an iron electrode battery may contain an iron active material as the main component of the negative electrode (i.e., more than 50% of the electrode active material is one or more iron active materials). Some examples of iron electrode batteries include nickel-iron batteries (NiOOH-Fe), manganese dioxide-iron batteries (MnO2-Fe), iron-air batteries (Fe-O2 batteries, which may include flow batteries or hybrid battery / fuel cell systems), silver-iron batteries (Ag-Fe), flow batteries such as all-iron flow batteries, or other batteries having electrodes that temporarily or permanently contain an iron active material. The term “manganese dioxide” encompasses a number of manganese oxide phases known to function as battery cathodes, such as gamma, delta, barnesite, or other manganese oxide phases produced by chemical processes or electrolysis or other synthesis processes.

[0028] Embodiments of the present invention include apparatus, systems, and methods for long-term and ultra-long-term low-cost energy storage. In this specification, “long-term” and / or “ultra-long-term” can refer to energy storage periods of 8 hours or more, such as 8-hour energy storage periods, energy storage periods ranging from 8 to 20 hours, 20-hour energy storage periods, energy storage periods ranging from 20 to 24 hours, 24-hour energy storage periods, energy storage periods ranging from 24 hours to 1 week, and energy storage periods ranging from 1 week to 1 year (e.g., from several days to several weeks or several months). In other words, a “long-term” and / or “ultra-long-term” energy storage cell refers to an electrochemical cell that can be configured to store energy over several days, several weeks, or several seasons. For example, an electrochemical cell may be configured to store energy generated by a solar cell during the summer months when sunlight is abundant and solar power exceeds grid requirements, and to discharge the stored energy during the winter months when sunlight may be insufficient to meet grid requirements.

[0029] Other embodiments include backup power supplies for telecommunications, data centers, electronic equipment, traffic signals, medical facilities, or buildings. The duration of power supply from the battery can range from a few minutes to several hours. The durations of energy storage and / or power supply described herein are provided as examples only and are not intended to be limiting.

[0030] Figure 1A shows examples of electrochemical cells that can be iron electrode batteries according to various embodiments. An electrochemical cell comprises a negative electrode, a positive electrode, an electrolyte, and a separator placed between the positive and negative electrodes (for example, as shown in Figure 1A). Figure 1A shows an example of an electrochemical cell 100, such as a battery, which includes a negative electrode and electrolyte 102 separated from the positive electrode and electrolyte 103 by a separator 104. The separator 104 may optionally be supported by a polypropylene mesh 105 of the cell 100 and a polyethylene or polypropylene frame 108. Current collectors 107 may be attached to the negative electrode 102 and the positive electrode 103 respectively and supported by a polyethylene or polypropylene backing plate 106. In some embodiments, the temperature of the electrochemical cell 100 may be controlled by insulation around the cell 100 and / or by a heater 150, etc. For example, the heater 150 can raise the temperature of the cell 100 and / or specific elements of the cell, such as the electrolytes 102, 103. The configuration of the electrochemical cell 100 shown in Figure 1A is merely an example of one electrochemical cell configuration according to various embodiments and is not intended to be limiting. Other configurations, such as electrochemical cells having and / or without the polypropylene mesh 105, electrochemical cells having and / or without the polyethylene frame 108, electrochemical cells having and / or without the current collector, electrochemical cells having a reservoir structure (such as one or more of the various sulfide reservoirs discussed in Pham Publication '702), electrochemical cells having and / or without the polyethylene backing plate 106, electrochemical cells having and / or without the insulator, and electrochemical cells having and / or without the heater 150 may be alternatives to the example configuration of the electrochemical cell 100 shown in Figure 1A, and other configurations depend on various embodiments.

[0031] In some embodiments, the multiple electrochemical cells 100 in Figure 1A may be electrically connected in series to form a stack. In certain other embodiments, the multiple electrochemical cells 100 may be electrically connected in parallel. In certain other embodiments, the multiple electrochemical cells 100 are connected in a series-parallel mixed electrical configuration to preferentially combine the supplied current and voltage.

[0032] According to various embodiments, the negative electrode is composed of an iron-containing material. The iron-containing material may be a pelletized, briquetteed, pressed, or sintered iron-containing compound. Such an iron-containing compound may contain one or more forms of iron ranging from highly reduced (more metallic) iron to highly oxidized (more ionic) iron. In various embodiments, the pellets may contain various iron compounds, such as iron oxide, iron hydroxide, iron sulfide, iron carbide, or combinations thereof. In various embodiments, the negative electrode may be a sintered iron-containing material having various shapes. In some embodiments, atomized iron powder or sponge iron powder can be used as the feed material for forming the sintered iron electrode. In some embodiments, the green body may further contain a binder, such as a polymer or an inorganic clay-like material. In various embodiments, the sintered iron-containing material pellets can be formed in furnaces such as continuous feed calcining furnaces, batch feed calcining furnaces, blast furnaces, rotary calcining furnaces, and rotary hearths. In various embodiments, the pellets may include in the form of a reduced and / or sintered iron-retaining precursor, and / or by-product material, known to those skilled in the art as directly reduced iron (DRI).

[0033] According to various embodiments, an electrochemical cell such as cell 100 in Figure 1A comprises a negative electrode (also called an anode), a positive electrode (also called a cathode), and an electrolyte. The negative electrode may be made of iron. The electrolyte may be an aqueous solution. In certain embodiments, the electrolyte may be an alkaline solution (pH > 10). In certain embodiments, the electrolyte may be a nearly neutral solution (pH > 4).

[0034] Figure 1B shows an example of an electrochemical cell that can be an iron electrode battery according to various embodiments. Figure 1B shows a secondary (rechargeable) battery system 10 comprising a positive electrode 12, a negative electrode 14, and a separator 16 in a battery container 18 filled with electrolyte 20 up to a level 22, which is at least the height of the upper parts 32, 34 of electrodes 12, 14. The space above the electrolyte level 22 is sometimes called the headspace 24. The positive electrode 12 may be electrically connected to the positive electrode terminal 42 of the battery and may contain an active material that undergoes a reduction reaction during discharge and an oxidation reaction during charging. The negative electrode 14 may be electrically connected to the negative electrode terminal 44 of the battery and may contain an active material that undergoes a reduction reaction during discharge and an oxidation reaction during charging of the battery 10. The configuration of the electrochemical cell in Figure 1B is merely an example of one electrochemical cell configuration according to various embodiments and is not intended to be limiting.

[0035] The negative electrode 14 active material may include metals or metal oxides such as iron, zinc, cadmium, or other metals, and / or oxides or hydroxides of these metals or other metals. In some embodiments, the iron negative electrode active material may include iron provided as elemental iron and / or iron-containing material (e.g., iron-containing alloys, or iron-containing compounds such as iron oxide, mixed iron oxides, iron hydroxide, iron sulfate, iron carbide, iron sulfide, or any combination thereof). In some embodiments, the iron negative electrode active material may include refined or smelted iron materials such as carbonyl iron or electrolytic iron, or iron ores such as magnetite, maghemite, iron carbonate, hematite, goetite, limonite, or other iron materials.

[0036] In some embodiments, the iron anode may contain carbonyl iron or other iron active material (e.g., magnetite, hematite, or other iron oxide or iron hydroxide) and two or more soluble metal sulfide additives in amounts of about 0.01% by weight (as a percentage of the weight of carbonyl iron) to 10% by weight or more. For example, the iron anode may contain iron active material, an iron sulfide additive in an amount of about 0.01% to about 10% by weight of the iron active material, and a second sulfide compound in an amount of about 0.01% to about 10% by weight of the iron active material (e.g., bismuth sulfide, iron sulfide, iron disulfide, iron-copper sulfide, zinc sulfide, manganese sulfide, tin sulfide, copper sulfide, cadmium sulfide, iron sulfide suboxide, silver sulfide, titanium disulfide, lead sulfide, molybdenum sulfide, nickel sulfide, antimony sulfide, dimethyl sulfide, carbon disulfide, etc.).

[0037] In various embodiments, the electrolyte 20 may be an aqueous or non-aqueous alkaline solution, a neutral solution, or an acidic solution. For example, the electrolyte solution may contain potassium hydroxide (KOH), sodium hydroxide (NaOH), lithium hydroxide (LiOH), or a combination thereof.

[0038] In some embodiments, the battery 10 may include a separator 16 configured to allow ion movement between electrodes 12, 14 via an electrolyte. In some embodiments, the separator may be selected based on its ability to allow selective movement of desired molecules or materials while substantially restricting or preventing the movement of unwanted molecules or materials. For example, some separator membranes are ion-selective, allowing the movement of anions (or cations) while substantially preventing the movement of cations (or anions). In other examples, the separator material may be selected based on its ability to allow or prevent the crossing of bubbles from one side (the side associated with one electrode) to the other side (the side associated with the opposing electrode).

[0039] In various embodiments, the battery container 18 may be made of any suitable material and structure capable of accommodating the electrolyte, electrodes, and at least a minimum amount of gas pressure. For example, the battery container 18 may be made of metal, plastic, composite material, etc. In some embodiments, the battery container 18 may be sealed to prevent leakage of gas generated during battery operation.

[0040] In some embodiments, the battery container 18 may include a pressure relief valve that releases gas when the gas pressure inside the battery container 18 exceeds a preset threshold.

[0041] Although electrodes 12 and 14 are substantially spaced apart in the figures, in some embodiments the electrodes may be very close to each other, or even compressed relative to each other with the separator 16 in between. Furthermore, although the figures may show one positive electrode 12 and one negative electrode 14, battery systems within the scope of this disclosure may also include two or more positive electrodes 12 and / or two or more negative electrodes 14.

[0042] Figure 1B also shows several examples of possible locations for the sulfide reservoirs (e.g., 58, 56, and / or 62) within or relative to the battery container. The examples of sulfide reservoir locations shown in Figure 1B are merely examples of configurations according to various embodiments and are not intended to be limiting. The sulfide reservoirs 58, 56, and / or 62 may be any type of reservoir structure, such as one or more of the various sulfide reservoirs discussed in Pham Publication '702.

[0043] To further extend the working life of nickel-iron batteries with minimal maintenance requirements, long-term reservoirs of soluble sulfides may be provided within the battery. As used herein, the term “sulfide reservoir” may also refer to sulfide ion sources other than “additive sulfides” and “integrated sulfides,” all of which are located within the iron anode and electrically connected to it. The “reservoir sulfide” may be located outside the iron electrode but electrically connected to it, located inside but electrically insulated or disconnected from the iron electrode, or located outside but electrically disconnected from the iron electrode. Sulfides may generally be released from the sulfide reservoir into the electrolyte by chemical reactions, electrochemical reactions, phase transition reactions, and / or controlled mechanical actions (e.g., the movement of servos, pistons, relays, or other electromechanical devices), or a combination of these mechanisms or other mechanisms.

[0044] In some embodiments, a closed-loop automatic control system may be configured to directly or indirectly detect conditions or events that suggest the need for sulfide addition to the electrolyte, and to supply or release a certain amount of sulfide source from a sulfide reservoir to the electrolyte when such events or conditions are detected. For example, in some embodiments, a sulfide detector (e.g., a sulfide ion selective electrode, an optical sulfide detector, etc.) may be connected to an automatic control device configured to periodically or continuously detect the sulfide concentration in the electrolyte with the sulfide detector. When a sulfide concentration below a threshold is detected, the control system can respond by activating an actuator device to supply sulfide source material to the electrolyte. For example, the actuator may be a pump, syringe, or plunger configured to supply a certain amount of solid or liquid sulfide source material to the electrolyte, for example, the same amount or a different amount each time.

[0045] In other embodiments, the automatic control system may be configured to detect one or more events that may indicate a need for sulfides in the electrodes. For example, an electronic control unit may be configured to monitor the performance of the cell and, in response to the detection of a low-sulfide event, activate an actuator to supply sulfide source material to the electrolyte. Examples of low-sulfide events include a decrease in Coulomb efficiency exceeding a threshold of change, a decrease in discharge rate capacity exceeding a threshold of quantity, prolonged overcharging (e.g., for a certain period of time or an overcharge of a predetermined amount in Coulombs), a change in electrolyte conductivity exceeding a threshold of quantity, or other events.

[0046] In some embodiments, low sulfide events may be chemically or electrochemically “detected” in such a way that they chemically or electrochemically trigger an autorelease of sulfides. In one embodiment, for example, the system is configured such that the detection or characterization of a low sulfide event is used as a trigger event to cause an “autorelease” of sulfides, and the autorelease is performed by, for example, an active or passive system or method for sulfide release.

[0047] In various embodiments, the actuator may be configured to release or supply a fixed amount of sulfide each time the actuator is triggered, or the actuator may be configured to release or supply an amount of sulfide proportional to a quantitative measurement of the trigger event.

[0048] In some embodiments, the sulfide reservoir may be configured to slowly release sulfide ions into the electrolyte at a location adjacent to the negative electrode in the battery, such that a substantial portion of the released sulfide ions reach the iron electrode and replace the consumed sulfides. In some embodiments, the sulfide source material for the sulfide reservoir may include one or more soluble metal sulfides, including iron sulfide (e.g., FeS, FeS2, Fe3S4 or other iron sulfide compounds or combinations thereof), zinc sulfide, manganese sulfide, lead sulfide, nickel sulfide, tin sulfide, bismuth sulfide, copper sulfide (CuS, Cu2S, or other copper sulfides), or cadmium sulfide, any polymorphs thereof, or combinations of these metal sulfides and / or other metal sulfides. In some embodiments, the sulfide source material for the sulfide reservoir is FeS 1-x O x It may contain one or more iron sulfide suboxides in the form of [unspecified form]. In some embodiments, the preferred material for the sulfide reservoir may include sparingly soluble metal sulfides, i.e., metal sulfides that release 10 mmol or less of sulfide ions per liter of electrolyte at temperatures up to 70°C.

[0049] In some embodiments, the sulfide reservoir may be configured to slow the rate of sulfide release from the reservoir to the electrolyte. The rate of sulfide release from the sulfide reservoir may be the dissolution rate if the reservoir is a solid sulfide source that releases sulfide by dissolution, the rate of electrochemical reduction if the reservoir is configured to release sulfide ions by an electrochemical reaction (e.g., by electrochemical reduction of a solid sulfide source electrically connected to the negative electrode), the injection or release rate of a liquid sulfide source, and / or the release and / or dissolution rate of a gaseous sulfur source (e.g., SO2 or H2S).

[0050] The dissolution rate of a solid sulfide reservoir in an aqueous alkaline battery electrolyte may be a function of, in particular, the surface area of ​​the sulfide reservoir exposed to the electrolyte, the dissolution rate of the sulfide source material, the diffusion rate and / or dissolution rate of the barrier surrounding the sulfide source material, the temperature of the electrolyte, the solubility limit (saturation limit) of the sulfide reservoir material, and the rate at which sulfides are removed from the electrolyte by absorption at the negative electrode or by irreversible conversion to sulfites or sulfates.

[0051] In some embodiments, the sulfide reservoir may be a “slow-release sulfide reservoir” in that it is configured to supply sulfide ions to the electrolyte at a slower rate than the natural dissolution rate of the same sulfide source material directly introduced into the electrolyte. In other words, a “slow-release” sulfide reservoir may have a sulfide ion release rate lower than the natural dissolution rate of the sulfide source material contained in the reservoir. Some embodiments of a slow-release sulfide reservoir may include structures and materials selected to dissolve and / or otherwise release sulfide ions at a predictably slow rate under the conditions expected to be experienced by a battery in operation. In some embodiments, the sulfide ion release rate may be approximately equal to the rate of sulfide consumption (e.g., conversion to sulfate ions by oxygen or the cathode), and as a result, the instantaneous sulfide concentration in the electrolyte at any given time or the average sulfide concentration over a period of time may be maintained within a desired range.

[0052] Figure 1B shows several alternative locations on the inside and outside of the battery container 18 where the sulfide reservoir may be installed, along with the corresponding ion and / or gas passages. For example, the sulfide reservoir may be located entirely or partially in the headspace 24 above the electrolyte level 22. Another exemplary embodiment is represented by a sulfide reservoir 56 in which part of the sulfide reservoir 56 is positioned so as to extend below the electrolyte level 22. In some embodiments, the sulfide reservoir 56 is firmly fixed to the battery container 18 (or another structure) at a fixed position relative to the electrolyte level 22. In some embodiments, the sulfide reservoir 58 may be located entirely below the electrolyte level. Figure 1B shows a sulfide reservoir 58 submerged below the electrolyte level 22. Figure 1B also shows a sulfide reservoir 62 located on the outside of the battery container 18. The sulfide reservoir 62 may be connected to the battery by an electrolyte conduit 66 extending between the sulfide reservoir 62 and the electrolyte 22 within the battery container 18.

[0053] The presence of sulfide compounds in iron electrode batteries can affect various performance indicators, including calendar life, cycle life, charge and / or discharge rate capacity; the ability of the electrodes to discharge relatively quickly; Coulomb efficiency; and self-discharge rate. Sulfides are thought to be involved in and / or facilitate intermediate reactions during the charging and / or discharging of iron electrodes. Furthermore, the sulfides involved in such reactions are thought to be primarily in the form of sulfide ions dissolved in aqueous electrolytes (alkaline or acidic aqueous solutions). Numerous electrolyte-soluble sulfide compounds can be used as source materials for sulfide uptake by iron electrodes. While various mechanisms have been proposed to precisely explain how sulfides benefit iron electrode batteries, the inventors have demonstrated a clear benefit of the sustained presence of sulfides on the long-term performance of iron electrode batteries.

[0054] Sulfides can be irreversibly lost from iron electrodes and electrolytes through multiple mechanisms under various conditions. Solid sulfides can be "lost" from iron electrodes by dissolution or electrochemical reduction, releasing sulfides into the bulk electrolyte. Dissolved sulfide ions can then be oxidized to sulfites or sulfates (or other sulfur compounds) upon encountering dissolved oxygen at the positive electrode or in the electrolyte. Oxidized sulfur species are not thought to be readily converted back to sulfides for participation in the iron electrode strengthening reaction.

[0055] The term "sulfide compound" refers to a chemical species that contains one or more sulfide ions, or a chemical species that, when dissolved in an electrolyte, can become one or more sulfide ions. Sulfide compounds may refer to "integrated sulfide" compounds, "additive sulfide" compounds, "sulfide source materials" in a "sulfide reservoir," or all of these (these terms are defined in Pham Publication '702 above). The term "sulfide ion" refers to S 2- or S 2- This refers to ions containing sulfide. Sulfide ions may exist in solid form as part of a solid compound (e.g., a solid ionic compound). Sulfide ions may also be dissolved sulfide ions, such as sulfide ions dissolved in an electrolyte. The term "sulfide" may refer to sulfide ions or sulfide ion-containing compounds. In some embodiments, the term "sulfide" refers to one or more sulfide ions. At least a portion of the additive sulfides in iron electrode batteries are in contact with the electrolyte.

[0056] The term "solubility limit" is generally understood to refer to the maximum amount of solute that can dissolve in a solvent at a given temperature and pressure. Solubility is expressed as the mass of solute per unit volume (g / L), the mass of solute per unit volume of solvent (g / g), or the moles of solute per unit volume (mol / L). A solution in which the maximum possible amount of solute at a given temperature has dissolved (i.e., when the solute concentration is equal to the solubility limit) is called "saturated." Generally, when a solution is saturated and an excess of solute is present, the rate of solute dissolution is equal to the rate of crystallization (or precipitation) of the solid solute. A solution in which more solute has dissolved than the solubility limit is called "supersaturated."

[0057] As used herein, the "concentration" of a dissolved ion species refers to the amount of ion species per unit volume and is usually expressed in moles of ions per liter (mol / L), also known as molar concentration, represented by the symbol "M".

[0058] As used herein, the terms “crystalline phase” and “crystalline form” refer to the crystalline structure of a crystallite, which is characterized by the unit cell or repeating structural pattern of the crystallite’s atoms. The term “crystallite” refers to a single crystal volume of a solid material having the same chemical composition and crystalline structure throughout its entire volume. A crystallite can be a grain, for example, a grain within a material such as a thin film or bulk material. A particle may be, for example, a single crystallite or may contain one or more crystallites. A solid solution precipitate may be, for example, a single crystallite or may contain one or more crystallites. In some cases, individual discrete particles may be a single crystallite. However, some particles may contain multiple crystallites separated by grain boundaries, surface boundaries, and / or amorphous regions. Each crystallite in a material, for example, a particle or thin film, may be separated from other crystallites by one or more surfaces, one or more particle boundaries (e.g., dislocations), one or more amorphous regions, one or more regions or volumes having different chemical compositions, one or more regions or volumes having different crystalline structures or polymorphs or phases, or any combination thereof.

[0059] Each cubic ZnS crystallite is formed of ZnS having a cubic crystal structure and is substantially (e.g., non-surface or ≤1 nm defects) or completely free of amorphous ZnS and crystalline hexagonal ZnS. In various embodiments of this specification, each crystalline cubic ZnS particle may consist solely of crystalline cubic ZnS and may be substantially free of amorphous ZnS, unstructured cubic ZnS, and hexagonal ZnS (e.g., having less than 50 mass%, less than 25 mass%, less than 10 mass%, less than 5 mass%, less than 1 mass%, less than 0.1 mass%, less than 0.01 mass%, less than 0.005 mass%, and less than 0.001 mass% of any combination of amorphous ZnS, unstructured cubic ZnS, and hexagonal ZnS).

[0060] Each cubic MnS crystallite is formed of MnS having a polymorphic or phase cubic crystal structure and is substantially (e.g., non-surface or ≤1 nm defects) or completely free of amorphous MnS and crystalline hexagonal MnS. In various embodiments of this specification, each crystalline cubic MnS particle may consist solely of crystalline cubic MnS and may be substantially free of amorphous MnS, unstructured cubic MnS, and hexagonal MnS (e.g., having any combination of amorphous MnS, unstructured cubic MnS, and hexagonal MnS in amounts less than 50 mass%, less than 25 mass%, less than 10 mass%, less than 5 mass%, less than 1 mass%, less than 0.1 mass%, 0.01 mass%, preferably less than 0.005 mass%, more preferably less than 0.001 mass%).

[0061] In this specification, the crystallite sizes and particle sizes described represent empirically derived grain and particle size characteristics, which are based on, determined by, or correspond to data from known techniques or apparatus in the art that can be used to determine crystal grain size or particle size, such as X-ray diffraction (XRD), electron microscopy (SEM and / or TEM), or light scattering methods (DLS, etc.). In embodiments, size characteristics correspond to physical dimensions such as cross-sectional size (e.g., length, width, thickness, diameter, etc.). In general, the terms “grain boundary,” “surface,” “crystallite,” “amorphous,” “unstructured,” and “particle” have meanings recognized by those skilled in the art of materials science.

[0062] As used herein, the term “crystallinity” has its usual meaning as understood by those skilled in the art, and represents the degree of atomic structural order in a solid material. Materials with high crystallinity have, on average, a longer range of atomic structural order than materials with low crystallinity. Materials with larger crystallites, on average, are characterized by higher crystallinity than materials with smaller crystallites. Crystallinity can be evaluated or determined using crystallographic techniques to determine material properties, such as one or more X-ray diffraction (XRD) techniques, and the broadening of one or more peaks (or peak widths) in the XRD pattern is inversely correlated with crystallinity and crystal size. For example, when comparing peaks at equivalent peak positions (2θ) and measurements are performed under otherwise identical conditions (e.g., same radiation, same apparatus, same temperature, etc.), larger crystallites of cubic ZnS (or cubic MnS) will have narrower XRD peaks compared to smaller crystallites of cubic ZnS (or MnS).

[0063] Among other methods, crystallite size can be empirically estimated using a method based on Scherrer's formula, which calculates crystallite size using XRD peak width. The crystallite size of a sample determined based on Scherrer's formula is sometimes called the "Scherrer size." Scherrer's formula (Equation 1) is:

number

[0064] Accordingly, with respect to the various embodiments described herein, the crystallinity of the sulfide additive material may be quantified by one or more indicators, such as referring to the "Scherrer size" of a sample of the material, referring to a measurement of the full width at half maximum of the XRD peak width at a peak characteristic of a particular crystalline morphology, or by other methods or combinations of methods. Crystallite size and / or crystallinity may also be quantified or approximated using other methods such as electron diffraction, such as transmission electron microscopy (TEM) or scanning electron microscopy (SEM).

[0065] As used herein, the term "crystalline" is used as an adjective to describe a material or particle having a sufficiently high degree of crystallinity to achieve a desired sulfide concentration in an electrolyte. In some cases, sufficiently high crystallinity may mean a degree of crystallinity exceeding a threshold of crystallinity measured by one or more of the techniques described above.

[0066] In contrast to "crystalline" materials, the term "unstructured" is used herein as an adjective to describe a material or particle having a low degree of crystallinity and / or containing a significant amount of amorphous phase material. In some cases, unstructured materials may have a degree of crystallinity below the threshold of crystallinity measured by one or more of the above indicators or techniques. Alternatively or in addition, unstructured materials can be defined as having an amount of amorphous phase material exceeding the threshold.

[0067] As used herein, the term “unstructured” (for example, in “unstructured cubic”) refers to a low, poor, or otherwise undesirable degree of crystallinity of a material for the applications conceived herein, in accordance with the embodiments and descriptions herein, and is not intended to suggest that the material completely or absolutely lacks atomic structure or crystallinity. As will become further apparent from the following discussion, a material, particle, sample, or other object characterized as “unstructured” (such as an unstructured cubic ZnS additive) may have a structure or crystallinity characterized by its structure or crystallinity (e.g., of the cubic phase) being undesirable to the particular embodiments and applications described herein (e.g., low crystallinity, overly broad XRD peaks, and / or too small average grain size by Scherrer's formula or Halder-Wagner method). As a mere example, a ZnS additive characterized by a Scherrer crystal size of less than 100 angstroms, or by a non-zero XRD peak having a full width at half maximum greater than approximately 0.4 degrees at approximately 28.6 degrees (2θ, CuK-α), is characterized as an unstructured cubic crystal.

[0068] In some cases, the amount of amorphous phase material can be determined or estimated using the same analytical tools as above, such as XRD, TEM, and SEM. Although amorphous phase material does not produce a specific peak on XRD, the amount of amorphous phase material in a test sample can be determined by comparing the XRD results with those of a sample containing known amounts of crystalline and amorphous material. Alternatively, the approximate amount of amorphous material in a sample may be estimated based on an analysis of its dissolution and reprecipitation behavior. When a sample containing low-crystallinity ZnS and / or amorphous ZnS is placed in a KOH electrolyte, it has been found that even if some cubic ZnS is present in the pre-dissolved sample, the excess dissolved material reprecipitations mainly in the form of hexagonal ZnS. Therefore, iron electrodes initially prepared with sulfide additives containing cubic ZnS and amorphous ZnS exceeding a threshold amount can be expected to have a detectable amount of hexagonal ZnS after a sufficient period of time (e.g., several days, weeks, months, or more after production). Alternatively, the amount of crystalline cubic material in the electrode can be determined by the following procedure. The electrode piece is rinsed to remove the electrolyte, dried, and analyzed by XRD at a scanning speed of 0.5-10 degrees / min. The XRD is then analyzed using the Rietveld method to obtain the mass fraction of cubic ZnS. Multiplying this by the molar mass of zinc divided by the molar mass of ZnS yields mass_Zn_cubic, which is the mass fraction of Zn in the sample as cubic ZnS. Another electrode piece is rinsed to remove the electrolyte, acid-digested, and analyzed by ICP-OES (inductively coupled plasma-atomography) to obtain mass_Zn_total, which is the mass fraction of Zn. The ratio of mass_Zn_cubic / mass_Zn_total is the mass percentage of the zinc sulfide additive in the form of cubic zinc sulfide.

[0069] Furthermore, this disclosure describes various materials or particles having high or low crystallinity of a particular crystalline phase. The term “unstructured cubic” refers to particles or materials having a cubic phase characterized by low crystallinity; “crystalline cubic” refers to particles or materials having a cubic phase and high crystallinity; “unstructured hexagonal” refers to particles or materials having a hexagonal phase characterized by low crystallinity; and “crystalline hexagonal” refers to particles or materials having a hexagonal phase characterized by high crystallinity.

[0070] Optionally, the term "unstructured cubic" refers to particles or materials having a cubic phase characterized by low crystallinity and / or amorphous material exceeding a threshold amount; "crystalline cubic" refers to particles or materials having a cubic phase as well as high crystallinity and less amorphous material than the threshold amount; "unstructured hexagonal" refers to particles or materials having a hexagonal phase characterized by low crystallinity and / or amorphous material exceeding a threshold amount; and "crystalline hexagonal" refers to particles or materials having a hexagonal phase characterized by high crystallinity and less amorphous material than the threshold amount.

[0071] For example, in some embodiments, a sample of ZnS or MnS (or other sulfide additive) may be considered "unstructured" if it has a cubic phase characterized by low crystallinity and more than 10% by weight of the sulfide additive material is in the amorphous phase. In other embodiments, the threshold amount of amorphous phase material sufficient to define a sulfide additive material as "unstructured" may be 20%, 25%, 30%, 40%, 50%, 60%, or more by weight of the sulfide additive, in addition to the sulfide additive material having a cubic phase characterized by low crystallinity.

[0072] Iron electrode batteries with excessively low sulfide electrolyte concentrations tend to suffer from low rate capacity, capacity degradation, high self-discharge rates, and other performance degradations. Conversely, high concentrations of sulfides in the electrolyte can also lead to performance degradation due to corrosion or other harmful effects on the iron electrodes.

[0073] Therefore, the key to realizing a high-performance iron electrode battery is to maintain the concentration of sulfide in the electrolyte within a narrow allowable range. The inventors have found that the ideal range of sulfide concentration is about 0.01 mmol / L to about 10 mmol / L. In some embodiments, the iron electrode battery has a sulfide (or S 2- ) concentration selected from the range of 0.01±20% mmol / L to 10±20% mmol / L before charging, during charging and / or discharging of the battery, and / or when the battery is in an open circuit and / or any other operating state. In some embodiments, the sulfide (or S 2- ) concentration of the electrolyte is lower than that generated by the presence of hexagonal ZnS in contact with the electrolyte, and higher than that generated by excess Bi2S3, CuS, PbS, Ir2S3, and / or CdS in contact with the electrolyte, which may be contained before charging, during charging and / or discharging of the battery, and / or when the battery is in an open circuit and / or any other operating state.

[0074] The service life of an iron electrode battery is largely determined by the time during which the battery can maintain the sulfide concentration within this range and the number of charge-discharge cycles. To achieve this, both the thermodynamic solubility limit and the kinetic dissolution rate are managed to replace the sulfide lost by conversion to other sulfur species, and the sulfide concentration can be maintained within the allowable range without supplying excess sulfide to the electrolyte. Several methods for achieving similar goals are described in the above-mentioned Pham Publication '702.

[0075] The "solubility limit" of a material refers to the maximum amount (or concentration) of a solute that can be dissolved in a solvent at a specified temperature and pressure. If the solution contains a solute at a concentration exceeding the solubility limit, the solute tends to precipitate. However, the actual concentration of the solute in the solution at any point in time is also a factor of the time-dependent dissolution and / or precipitation rate.

[0076] The soluble sulfides in the electrolyte at a given time point can be determined by taking a representative sample from the electrolyte, degassing the sample with argon, combining the sample with sulfide antioxidant buffer (SAOB) in a 1:1 volume ratio, and measuring the potential of this mixed sample using a sulfide ion-selective electrode (ISE) calibrated with a set of standardized sulfide solutions within a suitable concentration range within the past hour. The standardized sulfide solutions should narrow the range of sulfides of interest. For example, to measure with an accuracy of 1.0E-4M, a suitable standard can cover the range of 10E-6 to 10E-3M. The SAOB is preferably a fresh solution of 500 mL of 2 M NaOH and 18 g of ascorbic acid. Alternatively, total sulfur can be measured using ICP-OES in combination with an additional analytical step that distinguishes sulfides from oxide ion species, such as ion chromatography (IC). Using this second method (ICP-OES+IC or another method), the sulfide concentration is the difference between the total sulfur present in the solution and other sulfur oxide species. Since sulfides are reactive anions, all analysis must be performed within 4 hours of recovery. Alternatively, the sample should be prepared for storage by degassing with argon and then stored under an inert gas (i.e., nitrogen, argon) until testing.

[0077] U.S. Patent No. 4,250,236 to Haschka et al. ("Haschka") suggests that sulfide iron electrode additives may include the form of “slowly soluble” metal sulfides. Specifically, Haschka states that “two examples of [sulfide source additives] are zinc sulfide and manganese sulfide, and that ‘all known polymorphs of this are usable’” (Haschka, 4th column, lines 29-31, emphasis added). However, as the inventors have found, some polymorphs of ZnS exhibit significantly higher dissolution rates than expected in alkaline solutions, which can result in actual sulfide concentrations far exceeding the thermodynamic solubility limit, at least temporarily, leading to corrosion of the iron electrode, sulfide loss, and performance degradation over the entire lifespan of the iron electrode battery.

[0078] Published data and calculations on the solubility of zinc sulfide in 6M KOH alkaline solution indicate a solubility limit range of approximately 0.02 mM to approximately 0.7 mM. The inventor's own initial calculations suggest that the solubility limit of ZnS in 6M KOH is approximately 0.3 mM (i.e., 0.0003 mol of sulfide per liter of KOH electrolyte).

[0079] However, surprisingly, contrary to the above expectations, the inventors found unexpected dissolution behavior of ZnS in a 6M KOH solution. The inventors observed that the apparent solubility limit of ZnS increased with increasing amounts of ZnS added per unit volume of electrolyte, far exceeding the reported solubility limit suggested by published literature and the inventors' own initial calculations. The results are shown in the dataset in Figure 1C. While the inventors considered the possibility that ZnS simply dissolves unexpectedly in 6M KOH, they found another unexpected explanation. Although not bound by a specific operating theory, it is thought that some crystalline forms of ZnS produce sulfide concentrations exceeding the expected thermodynamic solubility limit due to differences in dissolution kinetics of various crystalline forms of ZnS, and / or because the differences in solubility limits of different crystalline forms are much larger than expected.

[0080] As shown in Figure 1C, the data suggest that the solubility of unstructured cubic ZnS is highly dependent on the ratio of solid ZnS to the volume of the electrolyte. Although not shown in Figure 1C, hexagonal ZnS (both unstructured and crystalline hexagonal ZnS) was found to exhibit a similar dependence on the solid-liquid ratio. In particular, crystalline cubic ZnS showed almost the same pattern, suggesting that it is more stable and / or less solubility.

[0081] Ultimately, the data suggest that unstructured cubic ZnS and hexagonal ZnS (both unstructured hexagonal ZnS and crystalline hexagonal ZnS) are about an order of magnitude more soluble in KOH than crystalline cubic ZnS. Another explanation is that some polymorphs of ZnS actually dissolve very quickly, so the dissolution rate outpaces the reprecipitation rate of ZnS, resulting in a sulfide concentration in the solution substantially exceeding the thermodynamic solubility limit of ZnS under the same conditions. We also found that when ZnS in any crystalline phase dissolves in KOH, it reprecipitations in a hexagonal crystalline form (typically low-crystallinity particles) that dissolves more quickly. Thus, rapid dissolution and reprecipitation in a rapidly dissolving crystalline form create an undesirable dissolution feedback loop, leading to undesirably high sulfide concentrations in the electrolyte.

[0082] The inventors have found that both unstructured and highly crystalline particles of the hexagonal wurtzite phase, upon dissolution, produce dissolved sulfide concentrations at least an order of magnitude higher than those obtained from the dissolution of highly crystalline particles of the cubic (or sphalerite) phase, under otherwise identical conditions. Surprisingly, low-crystallinity particles consisting of a cubic unit cell also exhibited very high dissolution rates, producing solutions with sulfide concentrations substantially exceeding the predicted thermodynamic solubility limit of cubic zinc sulfide. In fact, low-crystallinity cubic ZnS particles exhibited similar dissolution behavior to both low-crystallinity hexagonal ZnS and highly crystalline hexagonal ZnS particles.

[0083] After unstructured cubic zinc sulfide dissolved in the electrolyte solution, excess dissolved zinc sulfide (i.e., exceeding the thermodynamic solubility limit) reprecipitated as a solid. Surprisingly, the dissolved sulfide reprecipitated in the form of hexagonal crystals, which dissolve more quickly, thereby unnecessarily maintaining a high sulfide concentration in the electrolyte when hexagonal ZnS particles rapidly redissolve.

[0084] In contrast, crystalline cubic zinc sulfide particles were shown to dissolve substantially slower and have a lower apparent solubility limit than unstructured cubic particles, as shown in Figure 1C.

[0085] Crystalline cubic zinc sulfide with sufficiently high crystallinity is identified based on the full width at half maximum (FWHM) measurement of selected peaks in X-ray diffraction (XRD) scanning of zinc sulfide samples. Examples are shown in Figures 2A and 2B. Figure 2A is a schematic diagram of X-ray diffraction spectra representing two sample iron electrodes containing "unstructured" cubic zinc sulfide additives and "crystalline" zinc sulfide additives. In Figure 2A, label 200 represents a peak at 28.6 degrees, label 210 represents a peak at 47.6 degrees, label 220 represents a peak at 56.4 degrees, and label 230 represents a peak at 33.1 degrees. Samples with lower crystallinity show broader peaks at the positions corresponding to cubic ZnS. Such broad peaks can be quantified in terms of FWHM values, which are large for low-crystallinity samples and small (narrow) for high-crystallinity samples. In the description of each diffraction peak, a family of parallel crystal lattice planes that produce the diffraction peak, represented by the Miller index hkl, can be referenced. In Figure 2A, the peaks labeled 200, 210, 220, and 230 represent cubic zinc sulfide. The 28.6-degree peak labeled 200 has a Miller index of (111). The 33.1-degree peak labeled 230 has a Miller index of (200). The 47.6-degree peak labeled 210 has a Miller index of (220). The 56.4-degree peak labeled 220 has a Miller index of (311). The Miller index and peak angles are determined by the Rietveld method for ZnS in the cubic phase. Due to variance in the XRD measurement system, sample preparation, or other variability factors, the above peak positions may be identified by approximately + / - 0.1 degrees from the values ​​of the above positions.

[0086] Figure 2B shows an enlarged view of the peak labeled 200 in Peak Figure 2A. This figure also shows the full width at half maximum (FWHM) measurement, which is the measurement of the curve's width at half the maximum value (peak) of the curve. Due to variability in the XRD measurement system, sample preparation, user variability, or other variability factors, the measured FWHM value may vary by approximately + / - 0.05 degrees from the stated value. Unless otherwise stated, all XRD peak positions described herein correspond to 2θ degrees and CuK-α lines. When measuring peak positions and FWHM, the XRD is scanned at a speed ranging from 0.5 to 10 degrees / min, and the data are fitted using the Rietveld method.

[0087] The main crystalline phases or structures of ZnS are the cubic crystal, known as "sphalerite" or "sphalerite," and the hexagonal crystal, known as "wurtzite." In some embodiments, the terms "cubic zinc sulfide" and "crystalline cubic zinc sulfide" refer to zinc sulfide materials (e.g., one or more particles) that exhibit non-zero XRD peaks characteristic of cubic zinc sulfide, such as peaks 200, 210, 220, and 230 shown in Figures 2A and 3. For example, in some embodiments, crystalline cubic zinc sulfide exhibits one or more non-zero XRD peaks at the 2θ angle characteristic of cubic zinc sulfide, such as the non-zero XRD peak at about 28.6 degrees (2θ, CuK-α), with a full width at half maximum of less than about 0.4 degrees, less than about 0.3 degrees in other embodiments, less than about 0.2 degrees in other embodiments, and less than or equal to about 0.17 degrees in some specific embodiments. In some embodiments of crystalline cubic zinc sulfide, a non-zero XRD peak may be observed at one or more of the above peak positions, provided that when at least 0.01 g of granular ZnS material per 1 mL of electrolyte is placed in a 6 M KOH electrolyte solution, the material produces a dissolved sulfide concentration of less than 0.001 mol per liter after a soaking time of 200 hours.

[0088] In embodiments, "crystalline cubic ZnS" or "crystalline cubic zinc sulfide" may refer to cubic ZnS characterized by one or more of the following (having peaks characteristic of cubic zinc sulfide at nominal 28.6°, 47.6°, and 56.4° 2θ): (a) a non-zero XRD with a full width at half maximum of less than about 0.4° at about 28.6° (2θ, CuK-α), less than about 0.3° in other embodiments, less than about 0.2° in other embodiments, and less than or equal to about 0.17° in some specific embodiments. Peaks; (b) Non-zero XRD peaks having an FWHM value of less than approximately 0.5 degrees at approximately 47.6 degrees, less than approximately 0.4 degrees in other embodiments, less than approximately 0.3 degrees in other embodiments, and less than approximately 0.23 degrees in some specific embodiments; and / or (c) Non-zero XRD peaks having an FWHM value of less than approximately 0.6 degrees at approximately 56.4 degrees, less than approximately 0.5 degrees in other embodiments, less than approximately 0.4 degrees in other embodiments, less than approximately 0.3 degrees in other embodiments, and less than approximately 0.23 degrees in some specific embodiments.

[0089] The terms “unstructured cubic ZnS” or “unstructured cubic zinc sulfide” may refer to cubic ZnS that is not characterized or cannot be characterized as crystalline cubic ZnS or highly crystallinity cubic ZnS as described herein. In embodiments, “unstructured cubic ZnS” or “unstructured cubic zinc sulfide” may refer to cubic ZnS characterized by one or more of the following (having peaks characteristic of cubic zinc sulfide at nominal 28.6 degrees, 47.6 degrees, and 56.4 degrees 2θ): (a) a non-zero XRD peak at about 28.6 degrees (2θ, CuK-α) with a full width at half maximum of about 0.4 degrees or more; (b) a non-zero XRD peak at about 47.6 degrees with an FWHM of about 0.5 degrees or more; and / or (c) a non-zero XRD peak at about 56.4 degrees with an FWHM of about 0.6 degrees or more. Alternatively or additionally, “unstructured cubic ZnS” or “unstructured cubic zinc sulfide” may refer to ZnS compounds with a grain size of ≤25 nm by Scherrer method or ≤12 nm by Halder-Wagner method measured by XRD. Other techniques for measuring grain size, including but not limited to transmission electron microscopy and scanning electron microscopy, may be used to determine whether ZnS is “unstructured cubic ZnS” or “unstructured cubic zinc sulfide”. Different measurement methods may yield different grain size results, but the ability to roughly convert grain sizes between various techniques may be appropriately applied to convert XRD grain size measurements to appropriate grain sizes, and other characterization methods may be used to determine whether the ZnS material is “unstructured cubic ZnS” or “unstructured cubic zinc sulfide”.

[0090] Similarly, the terms “unstructured cubic manganese sulfide” and “crystalline cubic manganese sulfide” refer to manganese sulfide materials (e.g., particles or films) that exhibit non-zero XRD peaks characteristic of cubic manganese sulfide. For example, in some embodiments, crystalline cubic manganese sulfide exhibits one or more non-zero XRD peaks at a 2θ angle characteristic of cubic manganese sulfide, with a full width at half maximum of less than about 0.6 degrees, less than about 0.4 degrees in other embodiments, less than about 0.3 degrees in other embodiments, and less than or equal to about 0.2 degrees in some specific embodiments.

[0091] As used herein, the term “non-zero XRD peak” means a peak in a dataset that can be discovered, fitted, detected, or otherwise resolved from or above background noise or a baseline using one or more techniques or algorithms known in the art for discovering, fitting, detecting, or otherwise resolving peaks. A non-zero XRD peak has a finite FWHM greater than 0 and a finite peak area greater than 0.

[0092] Two untreated ZnS samples and three ZnS samples annealed under various conditions were evaluated by XRD, and the crystallite size was determined using Scherrer's formula. The untreated samples were found to be "unstructured" ZnS due to the presence of low-crystallinity cubic ZnS and amorphous phase ZnS. The "treated" samples were found to have sufficiently high crystallinity to produce the desired dissolution properties described herein. Using the same XRD scanning data, the crystallite size of the samples was calculated using two methods: directly applying Scherrer's formula as described above, and applying the Halder-Wagner method performed by Rigaku's PDXL software installed on the X-ray diffractometer used. The scanning data is summarized in Tables 1 and 2 below. The two methods yielded substantially different absolute values ​​for the same samples, but in each method, a clear difference can be seen between the structured and crystalline samples. The value of K used in the calculation of Scherrer's formula was 0.9, and the wavelength λ was 1.5406 angstroms. [Table 1] [Table 2]

[0093] Therefore, in some embodiments of the systems and methods herein, ZnS can be sufficiently crystallinity (hence referred to herein as crystalline cubic ZnS, or cubic ZnS characterized by high crystallinity) if the average crystallite size calculated by Scherrer's formula is approximately 250 Å or greater, approximately 300 Å or greater, approximately 400 Å or greater, approximately 500 Å or greater, approximately 600 Å or greater, approximately 700 Å or greater, or approximately 800 Å or greater. Alternatively, in some embodiments of the systems and methods herein, ZnS can be sufficiently crystallinity (hence referred to herein as crystalline cubic ZnS, or cubic ZnS characterized by high crystallinity) if the crystallite size measurements performed by the Halder-Wagner method are approximately 150 Å or greater, approximately 200 Å or greater, approximately 250 Å or greater, approximately 300 Å or greater, approximately 350 Å or greater, or approximately 400 Å or greater.

[0094] In some embodiments, the iron electrode battery can be substantially improved by including only crystalline cubic zinc sulfide particles as a sulfide source additive, such as those exhibiting the XRD FWHM values ​​characteristic of crystalline cubic ZnS as described herein. In various embodiments, crystalline cubic zinc sulfide may be included in the iron electrode as an additive in an amount of about 0.01 to about 20% by weight of the iron electrode. In some specific embodiments, crystalline cubic zinc sulfide may be included in the iron electrode as an additive in an amount of about 0.05 to about 10% by weight of the iron electrode, or about 0.1 to about 5% by weight of the iron electrode. In various embodiments, crystalline cubic zinc sulfide may be included in the iron electrode as an additive with a particle size of about 0.1 to about 500 microns, or in some embodiments about 0.1 to about 20 microns, or about 1 to 10 microns.

[0095] The presence of crystalline cubic zinc sulfide and / or crystalline cubic manganese sulfide additives in iron electrode batteries (where the additives are substantially or entirely free of amorphous zinc sulfide, amorphous manganese sulfide, unstructured zinc sulfide, unstructured manganese sulfide, hexagonal zinc sulfide, and / or hexagonal manganese sulfide) is conceivable herein to improve battery performance in several indices. For example, batteries having cubic zinc sulfide in iron electrodes tend to achieve improved cycle life, increased number of high discharge rate cycles (1C, 2C, 3C, or faster discharge rates), improved energy efficiency, improved Coulomb efficiency, improved charge retention, reduced self-discharge rate, and improved performance at high temperatures (e.g., as measured by any of the aforementioned indices). In some embodiments, using only highly crystalline cubic zinc sulfide and / or highly crystalline cubic manganese sulfide instead of unstructured cubic or hexagonal zinc sulfide and / or manganese sulfide can improve and / or simplify the electrode manufacturing process by reducing the solubility of the metal sulfide additive in the intermediate processing stage. Iron electrodes incorporating crystalline cubic zinc sulfide and / or crystalline cubic manganese sulfide can be manufactured by any suitable process, such as hot pressing, cold pressing, sintering, wet paste lamination, dry pressing, slurry coating, PTFE-based processes, roll bonding, tape casting (blade coating) pocket filling, or combinations thereof.

[0096] In some embodiments, crystalline cubic manganese sulfide (manganese breve) can be used in iron electrode batteries as a substitute for or in combination with zinc sulfide. When crystalline cubic manganese sulfide (MnS) is dissolved in alkaline battery electrolytes, it is expected to produce sulfide concentrations similar to those of crystalline cubic zinc sulfide (ZnS). As described above, crystalline cubic MnS can be distinguished from other crystalline forms of MnS by evaluating the FWHM value of selected peaks in X-ray diffraction analysis of a sample of the material.

[0097] In some embodiments, a certain amount of crystalline cubic zinc sulfide or cubic manganese sulfide may be used as a sulfide source material for an iron electrode battery that is exposed to the electrolyte but is physically and electrically disconnected from the iron electrode, instead of or in addition to crystalline cubic zinc sulfide or cubic manganese sulfide as additives in the iron electrode. A sulfide source material added to the electrolyte without being electrically connected to the iron electrode may be referred to herein as a “sulfide reservoir.”

[0098] The sulfide additives described herein have crystalline cubic ZnS and / or crystalline cubic MnS and may be added to iron electrodes or to iron electrodes during the manufacture of a battery having iron electrodes (e.g., by compounding with an iron active material, adding to an iron active material, or mixing with an iron active material). The sulfide additives may also be introduced in a manner that allows for subsequent activation by electrochemical or chemical methods. Optionally, the iron electrodes disclosed herein may include any combination of crystalline cubic ZnS and crystalline cubic MnS. Optionally, the iron electrodes may include low-solubility sulfide phases such as antimony sulfide, bismuth sulfide, cadmium sulfide, cerium sulfide, cobalt sulfide, copper sulfide, copper disulfide, indium sulfide, iron sulfide, iron disulfide, lead sulfide, manganese disulfide, mercury sulfide, molybdenum disulfide, nickel sulfide, silver disulfide, and tin sulfide. For example, iron electrodes may contain iron sulfide, manganese sulfide, tin sulfide, and zinc sulfide. ZnS and MnS materials may contain impurities. The impurity content may be <2%, <1%, <0.5%, <0.1%, or <0.01% by mass. The impurities may exist as dopants within the cubic ZnS lattice. Such dopants may cause a slight shift in the Bragg peak angle and / or expansion of the FWHM.

[0099] In various embodiments, crystalline cubic zinc sulfide can be produced by various processes depending on one or more starting materials or materials. For example, one method for producing crystalline cubic zinc sulfide from a zinc sulfide starting material of unknown crystalline morphology and crystallinity includes evaluating the starting material to determine the crystalline phase(s) and crystallinity of the starting material. As described above, the crystalline phase(s) of the starting material are determined by the position of the XRD peaks in the XRD scan. The crystallinity can be evaluated using the FWHM value of the peak corresponding to a given crystalline phase. Therefore, zinc sulfide having peaks at the above positions and with FWHM values ​​within the above range may already be usable in iron electrode batteries.

[0100] However, if the FWHM value is too high (corresponding to a broader peak and therefore undesirably low crystallinity or undesirably low average crystallite size), the starting material may be heat-treated to increase the degree of crystallinity and / or average crystallite size. Such heat treatment involves annealing the starting material by heating it in a vacuum or inert atmosphere (e.g., nitrogen, argon, or other inert gas) to a high temperature of at least about 400°C but lower than the melting point of ZnS, about 1850°C, for at least about 5 seconds or several hours, and then slowly cooling the material to room temperature. In some embodiments, the heat treatment may involve holding the material at a constant or fluctuating high temperature for 30 minutes, 1 hour, 2 hours, 3 hours, 4 hours, 5 hours or longer. In some specific embodiments, the heat treatment may involve heating the material to a temperature of 800°C to about 900°C, holding it for about 10 to 20 minutes, and then slowly cooling the material to room temperature. In some embodiments, heating and / or cooling may be carried out at a relatively slow rate, for example, about 10°C / min in some embodiments, about 5°C / min in some embodiments, or less than 5°C / min in some embodiments. In some embodiments, cooling to room temperature may occur by natural convection without controlling the rate of temperature decrease.

[0101] Alternatively, amorphous ZnS (and / or MnS), unstructured or low-crystallinity cubic ZnS (and / or MnS), and / or hexagonal ZnS (and / or MnS) starting materials may be heat-treated under conditions necessary to form and / or grow a cubic crystal structure to form crystalline cubic ZnS (and / or MnS) having the preferred high crystallinity described herein. In various embodiments, the heat treatment of the ZnS and / or MnS material may be carried out before, during, or after the production of the iron-electrode.

[0102] In some embodiments, crystalline cubic zinc sulfide may be prepared from raw materials containing zinc and sulfur. For example, in some embodiments, solid zinc sulfide may be chemically precipitated from an aqueous solution containing dissolved zinc and dissolved sulfur (from any suitable source material). In some embodiments, conditions of the precipitation reaction, such as temperature, reactant concentration, or inclusion of other additives, may be selected and controlled to produce a crystalline cubic zinc sulfide precipitate. In other embodiments, the precipitation reaction may be used to produce solid amorphous, unstructured, or low-crystallinity zinc sulfide particles, which may then be heat-treated as described herein to produce substantially crystalline cubic zinc sulfide only.

[0103] In other embodiments, crystalline cubic zinc sulfide may be produced by solid-state reactions at high temperatures (e.g., above 500°C) and under vacuum or an inert atmosphere using fine particulate (e.g., less than about 20 microns) solid zinc and sulfur raw materials.

[0104] In various embodiments, crystalline cubic MnS may be prepared using the same methods as those described above for the preparation of crystalline cubic ZnS. That is, crystalline cubic MnS may be prepared by annealing amorphous, unstructured, and / or low-crystallinity cubic MnS and / or hexagonal MnS at a temperature sufficient to achieve crystalline cubic MnS. Alternatively, crystalline cubic MnS may be prepared by controlling the rate at which MnS precipitates from a solution containing dissolved Mn and S species, or by a high-temperature (e.g., above about 500°C) reaction of Mn and S solids in a vacuum or inert atmosphere.

[0105] Various embodiments may include an electrochemical cell (e.g., 100, 10) such as a battery, having an iron anode (also called an iron negative electrode) and an electrolyte (e.g., 102, 103, 20) having a total hydroxide concentration greater than 3 M. In some embodiments, the electrolyte may have a total hydroxide concentration greater than 3 M and above the solubility limit of hydroxides in the electrolyte. In some embodiments, the total hydroxide concentration greater than 3 M contains more than 3 M of KOH + NaOH and more than 0.01 M of LiOH. In some embodiments, the electrolyte may have a total hydroxide concentration of 11 M or less. In some embodiments, the electrolyte may have a total hydroxide concentration of 11 M or less, or contain 1 M or less of LiOH or 10 M or less of KOH + NaOH. In some embodiments, if the electrolyte is KOH-based, the total hydroxide concentration may be greater than 4 M and less than 10 M. However, this disclosure is not limited to any particular electrolyte concentration.

[0106] Where used herein, unless otherwise specified, the term “specific gravity,” also known as apparent density, should be given the broadest possible meaning and generally refer to the weight per unit volume of a structure, such as the volumetric shape of a material. This property will include the internal porosity of the particles as part of their volume. This can be measured, among other techniques, with a low-viscosity fluid that wets the particle surface.

[0107] Where used herein, unless otherwise specified, the term “actual density,” sometimes also called true density, should be given the broadest possible meaning, generally referring to the weight per unit volume of a material when no voids are present in the material. This measurement and property essentially eliminates internal porosity from the material and does not include, for example, any voids in the material.

[0108] Therefore, the relationship between the three density properties can be explained using an aggregate of porous foam balls (e.g., Nerf® balls). The weight of the balls filling the container would be the bulk density of the balls:

number

[0109] The weight of a single ball per unit spherical volume is likely its apparent density.

number

[0110] The skeletal structure of the ball per unit volume of the remaining material, that is, the weight of the material constituting the ball after all void volume has been removed, would be the skeletal density.

number

[0111] Various embodiments of the use of iron are considered with respect to its use as a component of a battery (or cell) (e.g., 100, 10), as a material for a battery (or cell) (e.g., 100, 10) such as electrodes, and as combinations and variations thereof. In various embodiments, the iron material may be an iron powder such as gas atomized or water atomized powder or sponge iron powder. In various embodiments, the iron material may be in the form of pellets that are spherical or substantially spherical. In various embodiments, the iron material may be porous and may contain open and / or closed pores. In various embodiments, the iron material may include a material that has been further treated by hot or cold briquetting. Embodiments of iron material for use in the various embodiments described herein, including use as an electrode material, may have one, two or more, or all of the material properties listed in Table 3 below. As used herein, including in Table 3, the following terms have the following meanings unless otherwise expressly stated: “Specific surface area” means the total surface area per unit mass of the material, including the surface area of ​​pores in a porous structure; “Total Fe (weight %)” means the mass percentage of total iron relative to the total mass of the iron material; “Metallic Fe (weight %)” means the mass percentage of Fe relative to the total mass of the iron material. 0 This refers to the mass percentage of iron in its state. [Table 3]

[0112] * The specific surface area is preferably determined by the Brunauer-Emmett-Teller adsorption method ("BET"), more preferably BET as described in ISO 9277 (the disclosures in this document are incorporated herein by reference in their entirety). It is recognized that other tests, such as methylene blue (MB) staining, ethylene glycol monoethyl ether (EGME) adsorption, electrokinetic analysis of complex ion adsorption, and protein retention (PR) methods, can provide results that can be correlated with BET results.

[0113] **Skeleton density is preferably determined by the helium (He) gravity bottle method, more preferably as shown in ISO 12154 (the disclosures in this document are incorporated herein by reference in their entirety). It is recognized that other tests can be used to provide results that can be correlated with the results of the He gravity bottle method. Skeleton density may also be referred to in the art as “true density” or “actual density”.

[0114] *** The apparent density is preferably determined by immersion in water, and more preferably as shown in ISO 15968 (the disclosures in this document are incorporated herein by reference in their entirety). It is recognized that other tests can be used to provide results that can be correlated with the results of the He specific gravity bottle method. Porosity can be defined as the ratio of the apparent density to the actual density.

number

[0115] #Total Fe (wt%) is preferably determined by dichromate titration, more preferably as shown in ASTM E246-10 (the disclosures in this document are incorporated herein by reference in their entirety). It is recognized that other tests, such as titration after tin(II) chloride reduction, titration after titanium(III) chloride reduction, and inductively coupled plasma (ICP) spectroscopy, can provide results that can be correlated with those obtained by dichromate titration.

[0116] ##Metallic Fe (wt%) is preferably determined by iron(III) chloride titration, more preferably as shown in ISO 16878 (the disclosures in this document are incorporated herein by reference in their entirety). It is recognized that other tests, such as bromine-methanol titration, can be used to provide results that can be correlated with those obtained by iron(III) chloride titration.

[0117] Various embodiments of the use of directly reduced iron (DRI) as a material for batteries (or cells), as a component of batteries (or cells), and as combinations and variations thereof are considered. In various embodiments, DRI may be produced from or be a material obtained from the reduction of natural or processed iron ore, and such reduction is carried out without reaching the melting temperature of iron. In various embodiments, the iron ore may be taconite or magnetite or hematite or goethite, etc. In various embodiments, DRI may be in the form of pellets that are spherical or substantially spherical. In various embodiments, DRI may be porous and may contain open and / or closed pores. In various embodiments, DRI may include material that has been further treated by hot or cold briquetting. In various embodiments, DRI is obtained by reducing iron ore pellets to iron metal (Fe 0DRI can be produced by forming more metallic (more reduced, less oxidized) materials such as wustite (FeO), or composite pellets containing iron metal and residual oxide phases. In various non-limiting embodiments, DRI may be reduced iron ore taconite, directly reduced ("DR") taconite, reduced "blast furnace (BF) grade" pellets, reduced "electric arc furnace (EAF) grade" pellets, "cold directly reduced iron (CDRI)" pellets, directly reduced iron ("DRI") pellets, hot briquette iron (HBI), or any combination thereof. In the iron and steel industry, DRI is sometimes called "sponge iron," and its use is common, particularly in India. Embodiments of iron materials, including exemplary embodiments of DRI materials for use in the various embodiments described herein, including use as electrode materials, may have one, two or more, or all of the material properties listed in Table 4 below. As used herein, including in Table 4, the following terms have the following meanings unless otherwise expressly stated: “Specific surface area” means the total surface area of ​​the material per unit mass, including the surface area of ​​pores in porous structures; “Carbon content” or “Carbon (weight %)” means the mass of total carbon as a percentage of the total mass of DRI; “Cementite content” or “Cementite (weight %)” means the mass of Fe3C as a percentage of the total mass of DRI; “Total Fe (weight %)” means the mass of all iron as a percentage of the total mass of DRI; “Metallic Fe (weight %)” means the mass of Fe3C as a percentage of the total mass of DRI. 0 It means the mass of iron in its state; "metallized" is the percentage of the total mass of iron, Fe 0 This refers to the mass of iron in its state. As used herein, weight percentages, volume percentages, and apparent densities are understood to exclude any electrolytes or transient additives present in the pores unless otherwise stated.

[0118] Various embodiments can provide devices and / or methods for use in bulk energy storage systems, such as long-term energy storage (LODES) systems and short-term energy storage (SDES) systems. For example, various embodiments can provide batteries for bulk energy storage systems, such as batteries for LODES systems, batteries for SDES systems, and / or batteries for systems requiring power supply for any duration. Renewable energy sources are becoming increasingly widespread and cost-effective. However, many renewable energy sources face the problem of intermittency, which hinders their adoption. The impact of the intermittency tendency of renewable energy sources can be mitigated by pairing them with bulk energy storage systems such as LODES systems and SDES systems. To support the adoption of combined power generation, transmission, and storage systems (e.g., renewable power sources paired with bulk energy storage systems, and power plants having transmission equipment in either the power plant or the bulk energy storage system), there is a need for devices and methods to support the design and operation of such combined power generation, transmission, and storage systems, including the various embodiments of devices and methods described herein.

[0119] A combined-use power generation, transmission, and storage system may be a power plant comprising one or more power sources (e.g., one or more renewable power sources, one or more non-renewable power sources, or a combination of renewable and non-renewable power sources), one or more transmission facilities, and one or more bulk energy storage systems. The transmission facilities in either the power plant or / or bulk energy storage system may be optimized concurrently with the power generation and storage systems, or they may impose constraints on the design and operation of the power generation and storage systems. A combined-use power generation, transmission, and storage system can be configured to meet various output targets under various design and operational constraints.

[0120] Figures 4-12 show various exemplary systems in which one or more aspects of the various embodiments can be used as part of a bulk energy storage system such as a LODES system, an SDES system, or a system requiring power supply for any duration. For example, various embodiments described herein with reference to Figures 1A-3, such as electrochemical cells (or batteries) 100, 10, can be used as batteries for a bulk energy storage system such as a LODES system, an SDES system, or a system requiring power supply for any duration, and / or the various electrodes described herein can be used as components of a bulk energy storage system. As used herein, the term “LODES system” means a bulk energy storage system configured to have a rated duration (energy / power ratio) of 24 hours (h) or longer, such as a 24-hour duration, a 24-hour to 50-hour duration, a duration longer than 50 hours, a 24-hour to 150-hour duration, a duration longer than 150 hours, a 24-hour to 200-hour duration, a duration longer than 200 hours, a 24-hour to 500-hour duration, or a duration longer than 500 hours. As further examples, various embodiments of the electrochemical cells (or batteries) 100, 10 described herein with reference to Figures 1A-3 can be used as batteries for backup power systems such as those for telecommunications, data centers, electronic equipment, traffic signals, medical facilities, or buildings. The duration of power supply from the electrochemical cells (or batteries) 100, 10 may be any duration. The durations of energy storage and / or power supply described herein are generally and, in particular with reference to Figures 4-12, shown merely as examples and are not intended to be limiting.

[0121] Figure 4 shows an exemplary system in which one or more aspects of various embodiments can be used as part of a bulk energy storage system. Although Figure 4 is discussed in relation to an example of the LODES system 304, the duration of energy storage and / or power supply described with reference to Figure 4 is provided as an example only and is not intended to limit the scope of the invention or the claims. In a specific example, a bulk energy storage system incorporating one or more aspects of various embodiments may be the LODES system 304. For example, the LODES system 304 may include batteries of various embodiments described herein, various electrodes described herein, etc. The LODES system 304 may be electrically connected to a wind power station 302 and one or more power transmission facilities 306. The wind power station 302 may be electrically connected to the power transmission facility 306. The power transmission facility 306 may be electrically connected to a power distribution network 308. The wind power station 302 can generate electricity and can output the generated electricity to the LODES system 304 and / or power transmission facility 306. The LODES system 304 can store electricity received from the wind power station 302 and / or the power transmission equipment 306. The LODES system 304 can output the stored electricity to the power transmission equipment 306. The power transmission equipment 306 can output electricity received from either or both of the wind power station 302 and the LODES system 304 to the power distribution network 308, and / or receive electricity from the power distribution network 308 and output that electricity to the LODES system 304. Together, the wind power station 302, the LODES system 304, and the power transmission equipment 306 can constitute a power plant 300, which may be a combined power generation, transmission, and storage system. Electricity generated by the wind power station 302 may be directly transmitted to the power distribution network 308 via the power transmission equipment 306, or it may first be stored in the LODES system 304.In certain cases, the electricity supplied to the distribution network 308 may be entirely from the wind turbines 302, entirely from the LODES system 304, or from a combination of the wind turbines 302 and the LODES system 304. The distribution of electricity from the combined wind turbines 302 and the LODES system 304 power plant 300 may be controlled according to a predetermined long-term (multiple days or even more years) schedule, or according to the day-ahead (24-hour prior notice) market, or according to the hour-ahead market, or in response to real-time pricing signals.

[0122] As one example of the operation of power plant 300, the LODES system 304 can be used to reshape and "stabilize" the power produced by wind turbine 302. In one such example, wind turbine 302 may have a peak power output (capacity) of 260 megawatts (MW) and a capacity factor (CF) of 41%. The LODES system 304 may have a power rating (capacity) of 106 MW, a rated duration (energy / power ratio) of 150 hours (h), and a rated energy of 15,900 megawatt-hours (MWh). In another such example, wind turbine 302 may have a peak power output (capacity) of 300 MW and a capacity factor (CF) of 41%. The LODES system 304 may have a power rating (capacity) of 106 MW, a rated duration (energy / power ratio) of 200 hours, and a rated energy of 21,200 MWh. In another such example, wind power station 302 may have a peak power output (capacity) of 176 MW and a capacity factor (CF) of 53%. The LODES system 304 may have a power rating (capacity) of 88 MW, a rated duration (energy / power ratio) of 150 hours, and a rated energy of 13,200 MWh. In another such example, wind power station 302 may have a peak power output (capacity) of 277 MW and a capacity factor (CF) of 41%. The LODES system 304 may have a power rating (capacity) of 97 MW, a rated duration (energy / power ratio) of 50 hours, and a rated energy of 4,850 MWh. In yet another such example, wind power station 302 may have a peak power output (capacity) of 315 MW and a capacity factor (CF) of 41%. The LODES system 304 may have a power rating (capacity) of 110 MW, a rated duration (energy / power ratio) of 25 hours, and a rated energy of 2,750 MWh.

[0123] Figure 5 shows an exemplary system in which one or more aspects of various embodiments can be used as part of a bulk energy storage system. Although Figure 5 is discussed in relation to an example of the LODES system 304, the duration of energy storage and / or power supply described with reference to Figure 5 is provided as an example only and is not intended to limit the scope of the invention or the claims. In specific examples, a bulk energy storage system incorporating one or more aspects of various embodiments may be the LODES system 304. For example, the LODES system 304 may include batteries of various embodiments described herein, various electrodes described herein, etc. The system in Figure 5 may be similar to the system in Figure 4, except that a photovoltaic (PV) base station 402 may be used instead of a wind power base station 302. The LODES system 304 may be electrically connected to the PV base station 402 and one or more power transmission facilities 306. The PV base station 402 may be electrically connected to the power transmission facility 306. The power transmission facility 306 may be electrically connected to the power distribution network 308. The PV base station 402 can generate electricity and output the generated electricity to the LODES system 304 and / or the transmission equipment 306. The LODES system 304 can store the electricity received from the PV base station 402 and / or the transmission equipment 306. The LODES system 304 can output the stored electricity to the transmission equipment 306. The transmission equipment 306 can output the electricity received from either or both of the PV base station 402 and the LODES system 304 to the distribution network 308, and / or receive electricity from the distribution network 308 and output that electricity to the LODES system 304. Together, the PV base station 402, the LODES system 304, and the transmission equipment 306 can constitute a power plant 400, which may be a combined power generation, transmission, and storage system. The electricity generated by the PV base station 402 may be directly supplied to the distribution network 308 via the transmission equipment 306, or it may first be stored in the LODES system 304.In certain cases, the power supplied to the distribution network 308 may be entirely from the PV base station 402, entirely from the LODES system 304, or from a combination of the PV base station 402 and the LODES system 304. The distribution of power from the combined PV base station 402 and LODES system 304 power plant 400 may be controlled according to a predetermined long-term (multiple days or even more years) schedule, or according to the day-ahead (24-hour prior notice) market, or according to the hour-ahead market, or in response to real-time pricing signals.

[0124] As one example of the operation of power plant 400, the LODES system 304 can be used to reshape and "stabilize" the power produced by PV base station 402. In one such example, PV base station 402 may have a peak power output (capacity) of 490 MW and a capacity factor (CF) of 24%. The LODES system 304 may have a power rating (capacity) of 340 MW, a rated duration (energy / power ratio) of 150 hours, and a rated energy of 51,000 MWh. In another such example, PV base station 402 may have a peak power output (capacity) of 680 MW and a capacity factor (CF) of 24%. The LODES system 304 may have a power rating (capacity) of 410 MW, a rated duration (energy / power ratio) of 200 hours, and a rated energy of 82,000 MWh. In another such example, PV base station 402 may have a peak power output (capacity) of 330 MW and a capacity factor (CF) of 31%. LODES system 304 may have a power rating (capacity) of 215 MW, a rated duration (energy / power ratio) of 150 hours, and a rated energy of 32,250 MWh. In another such example, PV base station 402 may have a peak power output (capacity) of 510 MW and a capacity factor (CF) of 24%. LODES system 304 may have a power rating (capacity) of 380 MW, a rated duration (energy / power ratio) of 50 hours, and a rated energy of 19,000 MWh. In yet another such example, PV base station 402 may have a peak power output (capacity) of 630 MW and a capacity factor (CF) of 24%. The LODES system 304 may have a power rating (capacity) of 380 MW, a rated duration (energy / power ratio) of 25 hours, and a rated energy of 9,500 MWh.

[0125] Figure 6 shows an exemplary system in which one or more aspects of various embodiments can be used as part of a bulk energy storage system. Although Figure 6 is discussed in relation to an example of the LODES system 304, the duration of energy storage and / or power supply described with reference to Figure 6 is provided as an example only and is not intended to limit the scope of the invention or the claims. In specific examples, a bulk energy storage system incorporating one or more aspects of various embodiments may be the LODES system 304. For example, the LODES system 304 may include batteries of various embodiments described herein, various electrodes described herein, etc. The system in Figure 6 may be similar to the systems in Figures 4 and 5, except that both the wind power base 302 and the photovoltaic (PV) base 402 may be power generation devices operating together in a power plant 500. The PV base 402, wind power base 302, LODES system 304, and transmission equipment 306 together may constitute a power plant 500, which may be a combined power generation, transmission, and storage system. The electricity generated by the PV base station 402 and / or the wind power station 302 may be directly supplied to the distribution network 308 via the transmission equipment 306, or it may first be stored in the LODES system 304. In certain cases, the electricity supplied to the distribution network 308 may be supplied entirely from the PV base station 402, entirely from the wind power station 302, entirely from the LODES system 304, or from a combination of the PV base station 402, the wind power station 302, and the LODES system 304. The distribution of electricity from the combined wind power station 302, PV base station 402, and LODES system 304 power plant 500 may be controlled according to a predetermined long-term (multiple days or even more years) schedule, or according to the day-ahead (24-hour prior notice) market, or according to the hour-ahead market, or in response to real-time pricing signals.

[0126] As one example of the operation of power plant 500, the LODES system 304 can be used to reshape and "stabilize" the power produced by wind turbines 302 and PV turbines 402. In one such example, wind turbine 302 may have a peak power output (capacity) of 126 MW and a capacity factor (CF) of 41%, and PV turbine 402 may have a peak power output (capacity) of 126 MW and a capacity factor (CF) of 24%. The LODES system 304 may have a power rating (capacity) of 63 MW, a rated duration (energy / power ratio) of 150 hours, and a rated energy of 9,450 MWh. In another such example, wind turbine 302 may have a peak power output (capacity) of 170 MW and a capacity factor (CF) of 41%, and PV turbine 402 may have a peak power output (capacity) of 110 MW and a capacity factor (CF) of 24%. The LODES system 304 may have a power rating (capacity) of 57 MW, a rated duration (energy / power ratio) of 200 hours, and a rated energy of 11,400 MWh. In another such example, the wind power station 302 may have a peak power output (capacity) of 105 MW and a capacity factor (CF) of 51%, and the PV station 402 may have a peak power output (capacity) of 70 MW and a capacity factor (CF) of 31%. The LODES system 304 may have a power rating (capacity) of 61 MW, a rated duration (energy / power ratio) of 150 hours, and a rated energy of 9,150 MWh. In another such example, the wind power station 302 may have a peak power output (capacity) of 135 MW and a capacity factor (CF) of 41%, and the PV station 402 may have a peak power output (capacity) of 90 MW and a capacity factor (CF) of 24%. The LODES system 304 may have a power rating (capacity) of 68 MW, a rated duration (energy / power ratio) of 50 hours, and a rated energy of 3,400 MWh. In another such example, the wind power station 302 may have a peak power output (capacity) of 144 MW and a capacity factor (CF) of 41%, and the PV station 402 may have a peak power output (capacity) of 96 MW and a capacity factor (CF) of 24%.The LODES system 304 may have a power rating (capacity) of 72 MW, a rated duration (energy / power ratio) of 25 hours, and a rated energy of 1,800 MWh.

[0127] Figure 7 shows an exemplary system in which one or more aspects of various embodiments can be used as part of a bulk energy storage system. Although Figure 7 is discussed in relation to an example of the LODES system 304, the duration of energy storage and / or power supply described with reference to Figure 7 is provided as an example only and is not intended to limit the scope of the invention or the claims. In a specific example, a bulk energy storage system incorporating one or more aspects of various embodiments may be the LODES system 304. For example, the LODES system 304 may include batteries of the various embodiments described herein, various electrodes described herein, etc. The LODES system 304 may be electrically connected to one or more power transmission facilities 306. In this way, the LODES system 304 can operate in a “standalone” manner to arbitrage energy near market prices and / or avoid power transmission constraints. The LODES system 304 may be electrically connected to one or more power transmission facilities 306. The power transmission facilities 306 may be electrically connected to a distribution network 308. The LODES system 304 can store electricity received from the power transmission equipment 306. The LODES system 304 can output the stored electricity to the power transmission equipment 306. The power transmission equipment 306 can output the electricity received from the LODES system 304 to the distribution network 308, and / or receive electricity from the distribution network 308 and output that electricity to the LODES system 304.

[0128] The LODES system 304 and the transmission equipment 306 together can constitute a power plant 900. For example, the power plant 900 may be located downstream of the transmission constraints, closer to power consumption. In such an exemplary downstream power plant 600, the LODES system 304 may have a duration of 24 to 500 hours and may undergo one or more full discharges per year to support peak power consumption at times when transmission capacity is insufficient to provide services to customers. In addition, in such an exemplary downstream power plant 600, the LODES system 304 may undergo several shallow discharges (daily or more frequently) to arbitrage the difference between nighttime and daytime electricity prices and reduce the overall cost of electricity services to customers. As a further example, the power plant 600 may be located upstream of the transmission constraints, close to the point of generation. In such an exemplary upstream power plant 600, the LODES system 304 may have a duration of 24 to 500 hours and may undergo full charges once or more times a year to absorb excess generation when the transmission capacity is insufficient to distribute electricity to customers. In addition, in such an exemplary upstream power plant 600, the LODES system 304 may undergo several shallow charge-discharge cycles (daily or more frequently) to arbitrage the difference between nighttime and daytime electricity prices and maximize the value of the power generation equipment's output.

[0129] Figure 8 shows an exemplary system in which one or more aspects of various embodiments can be used as part of a bulk energy storage system. Although Figure 8 is discussed in relation to an example of the LODES system 304, the duration of energy storage and / or power supply described with reference to Figure 8 is provided as an example only and is not intended to limit the scope of the invention or the claims. In a specific example, a bulk energy storage system incorporating one or more aspects of various embodiments may be the LODES system 304. For example, the LODES system 304 may include batteries of the various embodiments described herein, various electrodes described herein, etc. The LODES system 304 may be electrically connected to commercial and industrial (C&I) customers 702 such as data centers and factories. The LODES system 304 may be electrically connected to one or more power transmission facilities 306. The power transmission facilities 306 may be electrically connected to a power distribution network 308. The power transmission facilities 306 can receive power from the power distribution network 308 and output that power to the LODES system 304. The LODES system 304 can store electricity received from the power transmission equipment 306. The LODES system 304 can output the stored electricity to the C&I customer 702. In this way, the LODES system 304 can reshape the electricity purchased from the distribution network 308 and operate it to match the consumption patterns of the C&I customer 702.

[0130] The LODES system 304 and the transmission equipment 306 can together constitute a power plant 700. As an example, the power plant 700 may be located near electricity consumption, i.e., near C&I customer 702, such as between the distribution network 308 and C&I customer 702. In such an example, the LODES system 304 may have a duration of 24 to 500 hours and may purchase electricity from the market when electricity is cheaper, thereby charging the LODES system 304. The LODES system 304 can then discharge when market prices are high to provide electricity to C&I customer 702, thus offsetting C&I customer 702's market purchases. As an alternative configuration, the power plant 700 may be located not between the distribution network 308 and C&I customer 702, but between renewable resources such as PV base stations and wind power base stations and the transmission equipment 306 which may be connected to these renewable resources. In such alternative examples, the LODES system 304 may have a duration of 24 to 500 hours, and the LODES system 304 may be charged at a time when renewable output may be available. The LODES system 304 can then discharge to cover part or all of the C&I customer 702's power demand, thereby providing the C&I customer 702 with electricity derived from renewable energy.

[0131] Figure 9 shows an exemplary system in which one or more aspects of various embodiments can be used as part of a bulk energy storage system. Although Figure 9 is discussed in relation to an example of the LODES system 304, the duration of energy storage and / or power supply described with reference to Figure 9 is provided as an example only and is not intended to limit the scope of the invention or the claims. In specific examples, a bulk energy storage system incorporating one or more aspects of various embodiments may be the LODES system 304. For example, the LODES system 304 may include batteries of various embodiments described herein, various electrodes described herein, etc. The LODES system 304 may be electrically connected to a wind power station 302 and one or more power transmission facilities 306. The wind power station 302 may be electrically connected to the power transmission facility 306. The power transmission facility 306 may be electrically connected to a C&I customer 702. The wind power station 302 can generate electricity and can output the generated electricity to the LODES system 304 and / or power transmission facility 306. The LODES system 304 can store electricity received from the wind power base 302.

[0132] The LODES system 304 can output the stored power to the transmission equipment 306. The transmission equipment 306 can output the power received from either or both of the wind turbine 302 and the LODES system 304 to the C&I customer 702. Together, the wind turbine 302, the LODES system 304, and the transmission equipment 306 can constitute a power plant 800, which may be a combined power generation, transmission, and storage system. The power generated by the wind turbine 302 may be supplied directly to the C&I customer 702 via the transmission equipment 306, or it may be first stored in the LODES system 304. In certain cases, the power supplied to the C&I customer 702 may be supplied entirely from the wind turbine 302, entirely from the LODES system 304, or from a combination of the wind turbine 302 and the LODES system 304. The LODES system 304 may be used to reshape the electricity generated by the wind turbine 302 to match the consumption patterns of the C&I customer 702. In one such example, the LODES system 304 may have a duration of 24 to 500 hours and may be charged when renewable power generation by the wind turbine 302 exceeds the load of the C&I customer 702. The LODES system 304 may then be discharged when renewable power generation by the wind turbine 302 falls below the load of the C&I customer 702, to provide the C&I customer 702 with a stable renewable profile that offsets some or all of the C&I customer 702's electricity consumption.

[0133] Figure 10 shows an exemplary system in which one or more aspects of various embodiments can be used as part of a bulk energy storage system. Although Figure 10 is discussed in relation to an example of the LODES system 304, the duration of energy storage and / or power supply described with reference to Figure 10 is provided as an example only and is not intended to limit the scope of the invention or the claims. In specific examples, a bulk energy storage system incorporating one or more aspects of various embodiments may be the LODES system 304. For example, the LODES system 304 may include batteries of various embodiments described herein, electrodes of various embodiments described herein, etc. The LODES system 304 integrates a large amount of renewable power into a microgrid, for example, harmonizing the output of renewable power from PV bases 402 and wind power bases 302 with existing thermal power from, for example, a thermal power plant 902 (e.g., a gas plant, a coal plant, a diesel generator set, etc., or a combination of thermal power generation methods), and may be part of a power plant 900 that supplies C&I customer loads 702 when availability is high. A microgrid, such as one comprising a power plant 900 and a thermal power plant 902, can provide an availability rate of 90% or higher. The electricity generated by the PV base 402 and / or wind power base 302 may be supplied directly to the C&I customer 702, or it may first be stored in the LODES system 304.

[0134] In certain cases, the electricity supplied to C&I customer 702 may be supplied entirely from PV terminal 402, entirely from wind power terminal 302, entirely from LODES system 304, entirely from thermal power plant 902, or from any combination of PV terminal 402, wind power terminal 302, LODES system 304, and / or thermal power plant 902. As an example, the LODES system 304 of power plant 900 may have a duration of 24 to 500 hours. In a specific example, the load on C&I customer 702 may have a peak of 100 MW, the LODES system 304 may have a power rating of 14 MW and a duration of 150 hours, the cost of natural gas may be $6 / million British pound thermal energy (MMBTU), and the renewable occupancy rate may be 58%. As another specific example, the C&I customer 702 load may have a peak of 100 MW, the LODES system 304 may have a power rating of 25 MW and a duration of 150 hours, the natural gas cost may be $8 per million British pound thermal energy (MMBTU), and the renewable occupancy rate may be 65%.

[0135] Figure 11 shows an exemplary system in which one or more aspects of various embodiments can be used as part of a bulk energy storage system. Although Figure 11 is discussed in relation to an example of a LODES system 304, the duration of energy storage and / or power supply described with reference to Figure 11 is provided as an example only and is not intended to limit the scope of the invention or the claims. In specific examples, a bulk energy storage system incorporating one or more aspects of various embodiments may be a LODES system 304. For example, a LODES system 304 may include batteries of various embodiments described herein, various electrodes described herein, etc. Using a LODES system 304, it is possible to enhance a nuclear power plant 1002 (or other inflexible power generation facilities such as thermal, biomass, and / or any other type of power plant with a ramp rate of less than 50% of rated power per hour and a capacity factor of 80% or higher) to add flexibility to the combined output of a power plant 1000 consisting of a combined LODES system 304 and a nuclear power plant 1002. The nuclear power plant 1002 can operate at a high capacity factor and at its highest efficiency point, and the LODES system 304 can be charged and discharged to effectively reshape the output of the nuclear power plant 1002 to match customer electricity consumption and / or the market price of electricity. As an example, the LODES system 304 of the power plant 1000 may have a duration of 24 to 500 hours. In one specific example, the nuclear power plant 1002 may have a rated output of 1,000 MW, and the nuclear power plant 1002 may be forced to perform minimum stable power generation or even shutdown for a long period due to a decline in the market price of electricity. The LODES system 304 can be charged to avoid facility shutdown when the market price falls, and then discharged when the market price rises to restore total output power generation.

[0136] Figure 12 shows an exemplary system in which one or more aspects of various embodiments can be used as part of a bulk energy storage system. Although Figure 12 is discussed in relation to examples of LODES system 304 and SDES system 1102, the duration of energy storage and / or power supply described with reference to Figure 12 is provided as an example only and is not intended to limit the scope of the invention or claims. As a specific example, a bulk energy storage system incorporating one or more aspects of various embodiments may be LODES system 304. For example, LODES system 304 may include batteries of various embodiments described herein, various electrodes described herein, etc. LODES system 304 can operate in conjunction with SDES system 1102. LODES system 304 and SDES system 1102 together may constitute a power plant 1100. As an example, the LODES system 304 and the SDES system 1102 can be optimized simultaneously, thereby enabling the LODES system 304 to provide various services, including long-term backup and / or bridging, over multi-day fluctuations (e.g., market prices, renewable power generation, electricity consumption, etc.). The SDES system 1102 can provide various services, including rapid auxiliary services (e.g., voltage control, frequency regulation, etc.) and / or bridging, over intraday fluctuations (e.g., market prices, renewable power generation, electricity consumption, etc.). The SDES system 1102 may have a duration of less than 10 hours and a round-trip efficiency greater than 80%. The LODES system 304 may have a duration of 24 to 500 hours and a round-trip efficiency greater than 40%. In one such example, the LODES system 304 may have a duration of 150 hours and can support customer electricity consumption for up to one week of renewable power shortages. Furthermore, the LODES system 304 can enhance the capacity of the SDES system 1102 by supporting the customer's electricity consumption during daytime power generation shortages.Furthermore, the SDES system 1102 can supply power to customers during daytime power shortage events and provide quality services such as power regulation, voltage control, and frequency regulation.

[0137] To illustrate various embodiments, several examples are shown below. Example 1: A battery electrode comprising an iron electrode body containing an iron active material and a zinc sulfide additive, wherein the zinc sulfide additive contains crystalline cubic zinc sulfide. Example 2: The electrode of Example 1, wherein the crystalline cubic zinc sulfide has a high degree of crystallinity when measured by at least one index. Example 3: The electrode of Example 1 or 2, wherein at least 75% by mass of the zinc sulfide additive is in the form of cubic zinc sulfide. Example 4: The electrode of Example 3, wherein at least 90% by mass of the zinc sulfide additive is in the form of cubic zinc sulfide. Example 5: The electrode of Example 4, wherein at least 99% by mass of the zinc sulfide additive is in the form of cubic zinc sulfide. Example 6: The electrode of Example 5, wherein 100% by mass of the zinc sulfide additive is in the form of cubic zinc sulfide. Example 7. One electrode from Examples 1 to 6, in which crystalline cubic zinc sulfide is characterized by a non-zero X-ray diffraction (XRD) peak with a full width at half maximum (FWHM) value of less than 0.4 ± 0.1 degrees at 28.6 ± 0.1 degrees. Example 8. One electrode from Examples 1 to 7, in which crystalline cubic zinc sulfide is characterized by a non-zero XRD peak with an FWHM value of less than 0.5 ± 0.1 degrees at 47.6 ± 0.1 degrees. Example 9. One electrode from Examples 1 to 8, in which crystalline cubic zinc sulfide is characterized by a non-zero XRD peak with an FWHM value of less than 0.6 ± 0.1 degrees at 56.4 ± 0.1 degrees. Example 10. One electrode from Examples 1 to 9, in which crystalline cubic zinc sulfide is present in the electrode as particles with a size of 0.1 microns to 500 microns. Example 11. Any one electrode from Examples 1 to 10, wherein crystalline cubic zinc sulfide is present in an amount of 0.01 to 20% by weight relative to the weight of the iron active material. Example 12. An iron electrode battery comprising an iron electrode and a sulfide reservoir separated from the iron electrode, wherein the sulfide reservoir contains crystalline cubic zinc sulfide. Example 13. The battery of Example 12, wherein the crystalline cubic zinc sulfide has a high degree of crystallinity when measured by at least one index. Example 14. The battery of Example 12 or 13, wherein at least 75% by mass of the zinc sulfide additive is in the form of cubic zinc sulfide. Example 15. The battery of Example 14, wherein at least 90% by mass of the zinc sulfide additive is in the form of cubic zinc sulfide. Example 16. The battery of Example 15, wherein at least 99% by mass of the zinc sulfide additive is in the form of cubic zinc sulfide.Example 17. The battery of Example 16, wherein 100% by mass of the zinc sulfide additive is in the form of cubic zinc sulfide. Example 18. The battery of any one of Examples 1 to 17, wherein the crystalline cubic zinc sulfide is characterized by a non-zero X-ray diffraction (XRD) peak with a full width at half maximum (FWHM) value of less than 0.4 ± 0.1 degrees at 28.6 ± 0.1 degrees. Example 19. The battery of any one of Examples 1 to 18, wherein the crystalline cubic zinc sulfide is characterized by a non-zero XRD peak with an FWHM value of less than 0.5 ± 0.1 degrees at 47.6 ± 0.1 degrees. Example 20. The battery of any one of Examples 1 to 19, wherein the crystalline cubic zinc sulfide is characterized by a non-zero XRD peak with an FWHM value of less than 0.6 ± 0.1 degrees at 56.4 ± 0.1 degrees. Example 21. Any one of the batteries from Examples 1 to 20, wherein crystalline cubic zinc sulfide is present in the electrode as particles with a size of 0.1 microns to 500 microns. Example 22. Any one of the batteries from Examples 1 to 21, wherein crystalline cubic zinc sulfide is present in an amount of 0.01 to 20% by weight of the iron active material. Example 23. Any one of the batteries from Examples 1 to 22, wherein the battery is selected from the group consisting of iron-air batteries, nickel-iron batteries, and iron-manganese dioxide batteries. Example 24. Any one of the batteries from Examples 1 to 23, comprising an electrolyte having a sulfide concentration selected from the range of 0.01 ± 20% mmol / L to 10 ± 20% mmol / L during battery operation. Example 25. A battery electrode comprising an iron electrode body containing an iron active material and a manganese sulfide additive, wherein the manganese sulfide additive contains crystalline cubic manganese sulfide. Example 26. The electrode of Example 25, wherein crystalline cubic zinc sulfide has a high degree of crystallinity when measured by at least one index. Example 27. The electrode of Example 25 or 26, wherein at least 75% by mass of the manganese sulfide additive is in the form of cubic manganese sulfide. Example 28. The electrode of Example 27, wherein at least 90% by mass of the manganese sulfide additive is in the form of cubic manganese sulfide. Example 29. The electrode of Example 28, wherein at least 99% by mass of the manganese sulfide additive is in the form of cubic manganese sulfide. Example 30. The electrode of Example 29, wherein 100% by mass of the manganese sulfide additive is in the form of cubic manganese sulfide. Example 31. Any one of the electrodes from Examples 25 to 30, wherein crystalline cubic manganese sulfide is present in the electrode as particles with a size of 0.1 microns to 500 microns.Example 32. Any one electrode from Examples 25 to 31, wherein crystalline cubic manganese sulfide is present in an amount of 0.01 to 20% by weight of the iron active material. Example 33. An iron electrode battery comprising an iron electrode and a sulfide reservoir separated from the iron electrode, wherein the sulfide reservoir contains crystalline cubic manganese sulfide. Example 34. The battery of Example 33, wherein crystalline cubic zinc sulfide has a high degree of crystallinity when measured by at least one index. Example 35. The battery of Example 33 or 34, wherein at least 75% by mass of the manganese sulfide additive is in the form of cubic manganese sulfide. Example 36. The battery of Example 35, wherein at least 90% by mass of the manganese sulfide additive is in the form of cubic manganese sulfide. Example 37. The battery of Example 36, wherein at least 99% by mass of the manganese sulfide additive is in the form of cubic manganese sulfide. Example 38. The battery of Example 37, wherein 100% by mass of the manganese sulfide additive is in the form of cubic manganese sulfide. Example 39. Any one of the batteries of Examples 33 to 38, wherein crystalline cubic manganese sulfide is present in the electrode as crystallites with a size of 0.1 microns to 500 microns. Example 40. Any one of the batteries of Examples 33 to 39, wherein crystalline cubic manganese sulfide is present in an amount of 0.01 to 20% by weight of the iron active material. Example 41. Any one of the batteries of Examples 1 to 40, wherein the battery is a member of the group consisting of iron-air batteries, nickel-iron batteries, and iron-manganese dioxide batteries. Example 42. Any one of the batteries of Examples 1 to 41, comprising an electrolyte having a sulfide concentration selected from the range of 0.01 ± 20% mmol / L to 10 ± 20% mmol / L. Example 43. A battery according to any one of Examples 1 to 42, comprising a positive electrode, a negative electrode, and at least one electrolyte, wherein the negative electrode includes an iron electrode from any one of Examples 1 to 42. Example 44. A method for manufacturing the battery according to any one of Examples 1 to 43, comprising the step of manufacturing an iron electrode body comprising an iron active material and a manganese sulfide additive and / or a zinc sulfide additive. Example 45. A method for manufacturing an electrode according to any one of Examples 1 to 44, comprising the step of manufacturing an iron electrode body comprising an iron active material and a manganese sulfide additive and / or a zinc sulfide additive. Example 46. The method of Example 44 or 45, comprising the step of combining a manganese sulfide additive and / or a zinc sulfide additive with an iron active material.Example 47. A method for operating one of the batteries from Examples 1 to 46, comprising the steps of: charging and / or discharging a battery, wherein the battery comprises a negative electrode, a positive electrode, and an electrolyte, and the negative electrode comprises an iron electrode from any one of Examples 1 to 46; and maintaining a sulfide concentration selected from the range of 0.01 ± 20% mmol / L to 10 ± 20% mmol / L during the charging and / or discharging steps. Example 48. One of the batteries from Examples 1 to 47, wherein before and / or during operation, the iron electrode contains less than 1 mass% of any combination of amorphous ZnS, unstructured cubic ZnS, crystalline hexagonal ZnS, amorphous MnS, unstructured cubic MnS, and crystalline hexagonal MnS. Example 49. One electrode from any of Examples 1 to 48, containing less than 1 mass% of any combination of amorphous ZnS, unstructured cubic ZnS, crystalline hexagonal ZnS, amorphous MnS, unstructured cubic MnS, and crystalline hexagonal MnS.

[0138] Example A. A battery electrode comprising an iron electrode body containing an iron active material and a zinc sulfide additive, wherein the zinc sulfide additive contains crystalline cubic zinc sulfide. Example B. The electrode of Example A, wherein the crystalline cubic zinc sulfide has a high degree of crystallinity when measured by at least one index. Example C1. The electrode of Example A or B, wherein at least 50% by mass of the zinc sulfide additive is in the form of cubic zinc sulfide. Example C2. The electrode of Example A or B, wherein at least 75% by mass of the zinc sulfide additive is in the form of cubic zinc sulfide. Example C3. The electrode of Example C2, wherein at least 90% by mass of the zinc sulfide additive is in the form of cubic zinc sulfide. Example D. The electrode of Example C2, wherein at least 95% by mass of the zinc sulfide additive is in the form of cubic zinc sulfide. Example E. The electrode of Example C3, wherein at least 99% by mass of the zinc sulfide additive is in the form of cubic zinc sulfide. Example F. The electrode of Example E, in which 100% by mass of the zinc sulfide additive is in the form of cubic zinc sulfide. Example G1. One electrode from Examples 1 to F, in which crystalline cubic zinc sulfide is characterized by a non-zero X-ray diffraction (XRD) peak with a full width at half maximum (FWHM) of less than 0.4 ± 0.1 degrees at 28.6 degrees for cubic ZnS with Miller index (111) when measured by the Rietveld method. Example G2. One electrode from Examples 1 to G1, in which crystalline cubic zinc sulfide is characterized by a non-zero X-ray diffraction (XRD) peak with a full width at half maximum (FWHM) of less than 0.6 ± 0.1 degrees at 28.6 degrees for cubic ZnS with Miller index (111) when measured by the Rietveld method. Example G3. A single electrode from Examples 1 to G2, characterized by a non-zero X-ray diffraction (XRD) peak at 28.6 degrees with a full width at half maximum (FWHM) of less than 0.45 ± 0.1 degrees for cubic ZnS with Miller index (111) when measured by the Rietveld method. Example G4. A single electrode from Examples 1 to G3, characterized by a non-zero X-ray diffraction (XRD) peak at 28.6 degrees with a full width at half maximum (FWHM) of less than 0.3 ± 0.1 degrees for cubic ZnS with Miller index (111) when measured by the Rietveld method.Example H1. Crystalline cubic zinc sulfide is one of the electrodes from Examples 1 to G4, characterized by a non-zero XRD peak with an FWHM value of less than 0.5 ± 0.1 degrees at 47.6 degrees for cubic ZnS with Miller index (220) when measured by the Rietveld method. Example H2. Crystalline cubic zinc sulfide is one of the electrodes from Examples 1 to H1, characterized by a non-zero XRD peak with an FWHM value of less than 0.45 ± 0.1 degrees at 47.6 degrees for cubic ZnS with Miller index (220) when measured by the Rietveld method. Example H3. Crystalline cubic zinc sulfide is one of the electrodes from Examples 1 to H2, characterized by a non-zero XRD peak with an FWHM value of less than 0.3 ± 0.1 degrees at 47.6 degrees for cubic ZnS with Miller index (220) when measured by the Rietveld method. Example H4. Crystalline cubic zinc sulfide is one of the electrodes from Examples 1 to H3, characterized by a non-zero XRD peak at 47.6°C with an FWHM value of less than 0.6 ± 0.1 degrees when measured by the Rietveld method for cubic ZnS with Miller index (220). Example H5. Crystalline cubic zinc sulfide is one of the electrodes from Examples 1 to H4, characterized by a non-zero XRD peak at 47.6°C with an FWHM value of less than 0.35 ± 0.1 degrees when measured by the Rietveld method for cubic ZnS with Miller index (220). Example H6. Crystalline cubic zinc sulfide is one of the electrodes from Examples 1 to H5, characterized by a non-zero XRD peak at 47.6°C with an FWHM value of less than 0.2 ± 0.1 degrees when measured by the Rietveld method for cubic ZnS with Miller index (220). Example I1. Crystalline cubic zinc sulfide is one of the electrodes from Examples 1 to H6, characterized by a non-zero XRD peak with an FWHM value of less than 0.6 ± 0.1 degrees at 56.4 degrees for cubic ZnS with Miller indices (311) when measured by the Rietveld method. Example I2. Crystalline cubic zinc sulfide is one of the electrodes from Examples 1 to I1, characterized by a non-zero XRD peak with an FWHM value of less than 0.45 ± 0.1 degrees at 56.4 degrees for cubic ZnS with Miller indices (311) when measured by the Rietveld method.Example I3. A single electrode from Examples 1 to I2, characterized by a non-zero XRD peak at 56.4 degrees with an FWHM value of less than 0.35 ± 0.1 degrees for cubic ZnS with Miller index (311) when measured by the Rietveld method. Example J1. A single electrode from Examples 1 to I3, characterized by a non-zero XRD peak at 33.1 degrees with an FWHM value of less than 0.6 ± 0.1 degrees for cubic ZnS with Miller index (200) when measured by the Rietveld method. Example J2. A single electrode from Examples 1 to J1, characterized by a non-zero XRD peak at 33.1 degrees with an FWHM value of less than 0.45 ± 0.1 degrees for cubic ZnS with Miller index (200) when measured by the Rietveld method. Example J3. Crystalline cubic zinc sulfide is one of the electrodes from Examples 1 to J2, characterized by a non-zero XRD peak with an FWHM value of less than 0.4 ± 0.1 degrees at 33.1 degrees for cubic ZnS with Miller index (200) when measured by the Rietveld method. Example J4. Crystalline cubic zinc sulfide is one of the electrodes from Examples 1 to J3, characterized by a non-zero XRD peak with an FWHM value of less than 0.3 ± 0.1 degrees at 33.1 degrees for cubic ZnS with Miller index (200) when measured by the Rietveld method. Example J5. Crystalline cubic zinc sulfide is one of the electrodes from Examples 1 to J4, characterized by a non-zero XRD peak with an FWHM value of less than 0.2 ± 0.1 degrees at 33.1 degrees for cubic ZnS with Miller index (200) when measured by the Rietveld method. Example K. One electrode from Examples 1 to J5, in which crystalline cubic zinc sulfide is present in the electrode as particles with a size of 0.1 microns to 500 microns. Example L. One electrode from Examples 1 to K, in which crystalline cubic zinc sulfide is present in an amount of 0.01 to 20% by weight relative to the weight of the iron active material. Example M. An iron electrode battery comprising an iron electrode and a sulfide reservoir separated from the iron electrode, the sulfide reservoir containing crystalline cubic zinc sulfide. Example N. The battery of Example M, in which crystalline cubic zinc sulfide has a high degree of crystallinity when measured by at least one index. Example O. The battery of Example M or N, in which at least 50% by mass of the zinc sulfide additive is in the form of cubic zinc sulfide.Example P. A battery of Example O, wherein at least 75% by mass of the zinc sulfide additive is in the form of cubic zinc sulfide. Example Q. A battery of Example P, wherein at least 90% by mass of the zinc sulfide additive is in the form of cubic zinc sulfide. Example R1. A battery of Example Q, wherein 95% by mass of the zinc sulfide additive is in the form of cubic zinc sulfide. Example R2. A battery of Example Q, wherein 99% by mass of the zinc sulfide additive is in the form of cubic zinc sulfide. Example R3. A battery of Example Q, wherein 100% by mass of the zinc sulfide additive is in the form of cubic zinc sulfide. Example S. A battery of any one of Examples 1 to R3, wherein the crystalline cubic zinc sulfide is characterized by a non-zero X-ray diffraction (XRD) peak with a full width at half maximum (FWHM) value of less than 0.4 ± 0.1 degrees at 28.6 ± 0.1 degrees. Example T. A battery from any of Examples 1 to S, in which crystalline cubic zinc sulfide is characterized by a non-zero XRD peak with an FWHM value of less than 0.5 ± 0.1 degrees at 47.6 ± 0.1 degrees. Example U. A battery from any of Examples 1 to T, in which crystalline cubic zinc sulfide is characterized by a non-zero XRD peak with an FWHM value of less than 0.6 ± 0.1 degrees at 56.4 ± 0.1 degrees. Example K. An electrode from any of Examples 1 to U, in which crystalline cubic zinc sulfide is present in the electrode as particles with a size of 0.1 microns to 500 microns. Example W. A battery from any of Examples 1 to V, in which crystalline cubic zinc sulfide is present in an amount of 0.01 to 20% by weight of the iron active material. Example X. A battery from any of Examples 1 to W, in which the battery is selected from the group consisting of iron-air batteries, nickel-iron batteries, and iron-manganese dioxide batteries. Example Y. A battery according to any one of Examples 1 to X, comprising an electrolyte having a sulfide concentration selected from the range of 0.01±20% mmol / L to 10±20% mmol / L during battery operation. Example Z. A battery electrode comprising an iron electrode body comprising an iron active material and a manganese sulfide additive, wherein the manganese sulfide additive comprises crystalline cubic manganese sulfide. Example AA. The electrode of Example Z, wherein the crystalline cubic manganese sulfide has a high degree of crystallinity when measured by at least one index. Example AB. The electrode of Example Z or AA, wherein at least 50% by mass of the manganese sulfide additive is in the form of cubic manganese sulfide. Example AC. The electrode of Example AB, wherein at least 75% by mass of the manganese sulfide additive is in the form of cubic manganese sulfide.Example AD: Electrode of Example AC, where at least 90% by mass of the manganese sulfide additive is in the form of cubic manganese sulfide. Example AE1: Electrode of Example AD, where 95% by mass of the manganese sulfide additive is in the form of cubic manganese sulfide. Example AE2: Electrode of Example AD, where 99% by mass of the manganese sulfide additive is in the form of cubic manganese sulfide. Example AE3: Electrode of Example AD, where 100% by mass of the manganese sulfide additive is in the form of cubic manganese sulfide. Example AF. Any one electrode from Examples Z to AE3, in which crystalline cubic manganese sulfide is present in the electrode as particles with a size of 0.1 microns to 500 microns. Example AG. Any one electrode from Examples Z to AF, in which crystalline cubic manganese sulfide is present in an amount of 0.01 to 20% by weight of the iron active material. Example AH. An iron electrode battery comprising an iron electrode and a sulfide reservoir separated from the iron electrode, wherein the sulfide reservoir contains crystalline cubic manganese sulfide. Example AI. The battery of Example AH, in which crystalline cubic manganese sulfide has a high degree of crystallinity when measured by at least one indicator. Example AJ. The battery of Example AH or AI, in which at least 50% by mass of the manganese sulfide additive is in the form of cubic manganese sulfide. Example AJ. The battery of Example AJ, in which at least 75% by mass of the manganese sulfide additive is in the form of cubic manganese sulfide. Example AK. A battery of Example AJ, in which at least 90% by mass of the manganese sulfide additive is in the form of cubic manganese sulfide. Example AL1. A battery of Example AK, in which 95% by mass of the manganese sulfide additive is in the form of cubic manganese sulfide. Example AL2. A battery of Example AK, in which 99% by mass of the manganese sulfide additive is in the form of cubic manganese sulfide. Example AL3. A battery of Example AK, in which 100% by mass of the manganese sulfide additive is in the form of cubic manganese sulfide. Example AM. A battery of any one of Examples AH to AL3, in which crystalline cubic manganese sulfide is present in the electrode as crystallites with a size of 0.1 microns to 500 microns. Example AN. A battery of any one of Examples AH to AM, in which crystalline cubic manganese sulfide is present in an amount of 0.01 to 20% by weight of the iron active material. Example AO. A battery from any one of Examples 1 to AN, which is a member of the group consisting of iron-air batteries, nickel-iron batteries, and iron-manganese dioxide batteries. Example AP. A battery from any one of Examples 1 to AO, which contains an electrolyte having a sulfide concentration selected from the range of 0.01 ± 20% mmol / L to 10 ± 20% mmol / L. Example AQ. A battery from any one of Examples 1 to AP, which comprises a positive electrode, a negative electrode, and at least one electrolyte, wherein the negative electrode contains an iron electrode from any one of Examples 1 to AP.Example AR. A battery according to any one of Examples 1 to AQ, comprising a positive electrode, a negative electrode, and at least one electrolyte, wherein the negative electrode comprises antimony sulfide, bismuth sulfide, cadmium sulfide, cerium sulfide, cobalt sulfide, copper sulfide, copper disulfide, indium sulfide, iron sulfide, iron disulfide, lead sulfide, manganese disulfide, mercury sulfide, molybdenum disulfide, nickel sulfide, silver disulfide, and tin sulfide. Example AS. A method for manufacturing the battery according to any one of Examples 1 to AR, comprising the step of manufacturing an iron electrode body comprising an iron active material and at least one of a manganese sulfide additive and a zinc sulfide additive. Example AT. A method for manufacturing an electrode according to any one of Examples 1 to AS, comprising the step of manufacturing an iron electrode body comprising an iron active material and at least one of a manganese sulfide additive and a zinc sulfide additive. Example AU. The method of Example AS or AT, comprising the step of combining a manganese sulfide additive and / or a zinc sulfide additive with an iron active material. Example AV. A method of operating one of the batteries of Examples 1 to AU, comprising the steps of charging and / or discharging a battery, wherein the battery comprises a negative electrode, a positive electrode, and an electrolyte, and the negative electrode comprises an iron electrode of any one of Examples 1 to AU; and maintaining a sulfide concentration selected from the range of 0.01±20% mmol / L to 10±20% mmol / L during the charging and / or discharging steps. Example AW. One of the batteries of Examples 1 to AV, wherein before and / or during operation, the iron electrode contains less than 1 mass% of any combination of amorphous ZnS, unstructured cubic ZnS, crystalline hexagonal ZnS, amorphous MnS, unstructured cubic MnS, and crystalline hexagonal MnS. Example AX. One electrode from Examples 1 to AW containing less than 1 mass% of any combination of amorphous ZnS, unstructured cubic ZnS, crystalline hexagonal ZnS, amorphous MnS, unstructured cubic MnS, and crystalline hexagonal MnS. Example AY. A bulk energy storage system comprising one or more electrodes and / or one or more batteries as described in Examples A to AX. Example AZ. A long-term energy storage system configured to retain charge for at least 24 hours, comprising one or more electrodes and / or one or more battery systems as described in Examples A to AX.

[0139] Any aspect and embodiment disclosed herein may be combined with any aspect and embodiment disclosed in Pham Publication '702, which is referenced above.

[0140] While the present invention has been disclosed with respect to certain preferred embodiments and examples, those skilled in the art will understand that the invention extends beyond the specifically disclosed embodiments to other alternative embodiments and / or uses of the invention, as well as obvious modifications and equivalents thereof. Various modifications to the above embodiments will be immediately apparent to those skilled in the art, and the basic principles set forth herein can be applied to other embodiments without departing from the spirit or scope of the invention. Accordingly, the scope of the invention disclosed herein is not limited to the specific disclosed embodiments described above and is intended to be determined solely by a fair reading of the following claims.

[0141] The term “substantially” refers to a characteristic, condition, or value that is within 20%, 10%, 5%, 1%, optionally 0.1%, or equivalent to the referenced characteristic, condition, or value. The terms “substantially equal,” “substantially equivalent,” or “substantially unchanged” refer to a value that, when used with a reference value describing a characteristic or condition, is within 20%, 10%, optionally 5%, optionally 1%, optionally 0.1%, or optionally equivalent to the given reference value. For example, if the diameter value is within 20%, optionally 10%, optionally 5%, optionally 1%, optionally 0.1%, or optionally equivalent to 100 nm, then the diameter is substantially equal to 100 nm (or “substantially 100 nm”). The term “substantially larger,” when used with a reference value describing a characteristic or condition, refers to a value that is at least 1%, optionally at least 5%, optionally at least 10%, or optionally at least 20% larger than the given reference value. The term “substantially smaller,” when used with a reference value describing a characteristic or condition, refers to a value that is at least 1%, optionally at least 5%, optionally at least 10%, or optionally at least 20% smaller than the given reference value. As used herein, the terms “about” and “substantially” are interchangeable and have the same meaning. For example, a particle with a size of about 1 μm is understood to have a size of within 20%, optionally within 10%, optionally within 5%, optionally within 1%, optionally within 0.1%, or optionally equal to 1 μm.

[0142] In particular, materials and manufacturing techniques may be used within the scope of a person skilled in the art. Furthermore, references to singular items include the possibility that there may be multiple identical items. More specifically, when used herein and in the appended claims, the singular “one,” “and,” “above / above,” and “the” (“a,” “and,” “said,” and “the”) include multiple references unless the context explicitly states otherwise. When used herein, unless otherwise explicitly stated, the term “or” includes all alternatives presented and has essentially the same meaning as the phrase “and / or.” Note that claims may be drafted to exclude any optional element. Thus, this statement is intended to serve as an antecedent for the use of exclusive terms such as “exclusively,” “only,” or “negative” limitation in relation to the enumeration of elements of the claims. Unless otherwise defined herein, all technical and scientific terms used herein have the same meaning as commonly understood by a person skilled in the art to which the invention belongs.

[0143] As used in this specification and in the claims, the terms “and / or” refer to only one element from the list in which the term “and / or” is listed, or any combination of elements. In other words, a list of two or more elements containing the term “and / or” is intended to cover embodiments having any of the individual elements alone, or any combination of the listed elements. For example, the phrase “element A and / or element B” is intended to cover embodiments having only element A, only element B, or both element A and element B together. For example, the phrase “element A, element B, and / or element C” is intended to cover embodiments having only element A, only element B, only element C, or elements A and B together, elements A and C together, elements B and C together, or elements A, B, and C together.

[0144] The term "±" refers to a range of values, such as "X±Y," where X and Y are independent numbers, and the range of values ​​selected from the range XY to X+Y is used.

[0145] Where used herein, unless otherwise specified, the enumeration of value ranges herein is intended merely as a simplified way of referring individually to each separate value that falls within the range. Unless otherwise indicated herein, each individual value within the range is incorporated herein as if it were individually enumerated herein.

Claims

1. The device comprises an iron electrode body containing an iron active material and a zinc sulfide additive, The aforementioned zinc sulfide additive is Crystalline cubic zinc sulfide is present in an amount of 0.01% to 20% by weight relative to the weight of the iron active material, During charging, the sulfide ion concentration is 0.01 mmol / L to 10 mmol / L, and the electrolyte contains sulfide ions that can be released from the crystalline cubic zinc sulfide to an electrolyte with a pH greater than 4. battery electrode.

2. The average crystallite size of the aforementioned crystalline cubic zinc sulfide is approximately 250 Å or larger, as calculated by Scherrer's formula. The battery electrode according to claim 1.

3. The battery electrode according to claim 1, wherein at least 50% by mass of the zinc sulfide additive is in the form of cubic zinc sulfide.

4. The battery electrode according to claim 3, wherein at least 75% by mass of the zinc sulfide additive is in the form of cubic zinc sulfide.

5. The battery electrode according to claim 4, wherein at least 90% by mass of the zinc sulfide additive is in the form of cubic zinc sulfide.

6. The battery electrode according to claim 1, characterized in that the crystalline cubic zinc sulfide has a non-zero X-ray diffraction (XRD) peak corresponding to the Miller index (111) of cubic ZnS measured by the Rietveld method, the non-zero X-ray diffraction peak appears at 2θ = 28.6 degrees in the CuK-α line, and the full width at half maximum (FWHM) value is less than 0.6 ± 0.1 degrees.

7. The battery electrode according to claim 1, characterized in that the crystalline cubic zinc sulfide has a non-zero X-ray diffraction peak (XRD) corresponding to the Miller index (220) of cubic ZnS measured by the Rietveld method, the non-zero X-ray diffraction peak appears at 2θ = 47.6 degrees in the CuK-α line, and the full width at half maximum (FWHM) is less than 0.5 ± 0.1 degrees.

8. The battery electrode according to claim 1, characterized in that the crystalline cubic zinc sulfide has a non-zero X-ray diffraction peak (XRD) corresponding to the Miller index (311) of cubic ZnS measured by the Rietveld method, the non-zero X-ray diffraction peak appears at 2θ = 56.4 degrees in the CuK-α line, and the full width at half maximum (FWHM) is less than 0.6 ± 0.1 degrees.

9. The battery electrode according to claim 1, characterized in that the crystalline cubic zinc sulfide has a non-zero X-ray diffraction peak (XRD) corresponding to the Miller index (200) of cubic ZnS measured by the Rietveld method, the non-zero X-ray diffraction peak appears at 2θ = 33.1 degrees in the CuK-α line, and the full width at half maximum (FWHM) is less than 0.6 ± 0.1 degrees.

Citation Information

Patent Citations

  • Cathode for sodium-metal halide battery, battery comprising the same, methods for preparing the same and use thereof

    EP2690685A1

  • N-type group ii-vi compound semiconductor film and its manufacturing method

    JP2009059968A

  • Cathode for sodium-metal halide battery, battery comprising the same, methods for preparing the same and use thereof

    US20140030596A1

  • Systems and methods for a battery

    US20170207432A1

  • Display device

    WO2008102559A1